Curable film composition, curable film, and cured product thereof
Patent Information
- Application Number
- KR1020250037804
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2025-03-25
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-02-15
Smart Images

Figure 112025033627013-PAT00011_ABST
Abstract
Description
Technology Field
[0001] Cross-reference regarding related applications
[0002] This specification is an extension of U.S. Patent Application No. 18 / 110,949 filed on February 17, 2023, the full disclosure of which is incorporated herein by reference.
[0003] Technology field
[0004] The present invention relates to a composition for a curable film; a curable film prepared therefrom; a cured product obtained by curing the curable film; and a method for preparing a curable film. The curable film is thin, has a significantly light weight, and excellent processability. The cured product thereof has desirable dielectric and thermomechanical properties suitable as a circuit material for manufacturing, for example, a printed circuit board (PCB). Accordingly, the curable film can be used to replace prepreg with favorable results. The present invention also relates particularly to a PCB dielectric layer prepared from a curable film for multilayer PCBs and HDI PCBs. Background Technology
[0005] For example, the need for high data transfer rate support for high-speed computers, and the demand for small and / or lightweight electronic devices, e.g., mobile devices, IoT devices, autonomous systems for autonomous vehicles and drones (LiDAR, radar and cameras), and electronic components for medical equipment and military communication equipment, 5G applications, etc., have led to the search for new insulators for circuit materials.
[0006] Printed circuit boards (PCBs) are used in almost all electronic products today. A basic PCB consists of a flat sheet of insulating material (dielectric layer) and a layer of copper foil laminated onto a substrate. PCBs can be single-sided (one copper layer), double-sided (two copper layers), or multilayer, allowing for high component density. Multilayer PCBs, which became more common in the 1990s, are complex composite structures typically containing a series of layers of reinforcing resin and copper foil. Conductors on different layers can be connected vias or plated through-holes. High-density interconnect (HDI) technology enables designs with much higher density within a given area on a PCB. Multilayer HDI PCBs are not only denser but also feature fewer layers, lighter weight, smaller vias, pads, copper traces, and spacing. Furthermore, by shortening the distance between devices and trace space, HDI PCBs allow more transistors to be installed, improving the performance of electronic devices while simultaneously lowering power consumption. Signal integrity is also improved due to shorter connection distances and lower power requirements. As a result, denser and smaller PCBs with improved performance become possible.
[0007] There are three common HDI structures. The first structure is n having one layer built on both sides of a core assembly comprising layers 1 + n + 1 It is a structure. Typically, n The lowest value of is 2. The second structure is i + n + i It is a structure, and here, i is greater than 2. This is n On both sides of the layer core assembly i It refers to a structure (build) of several layers, where, iis 2 or greater. Example i + n + i The HDI PCB is exemplified in FIG. 1a, where the middle layer is a glass-reinforced core with 6 layers (i.e., n = 6) and the outer 4 layers (i.e., i = 4) The layer is a glass-reinforced prepreg-based layer. The third structure is an arbitrary-layer HDI PCB in which all layers can be interconnected using copper-filled vias. Arbitrary-layer HDI PCBs are typically used in mobile devices. An example of an arbitrary-layer HDI PCB configuration is illustrated in FIG. 1b, where the middle core is a double-sided glass-reinforced laminate and the outer layer is a glass-reinforced prepreg-based layer.
[0008] As the demand for component miniaturization, mobile computing, and 5G applications continues to grow, HDI PCBs utilize the latest technology to further reduce area while increasing the functionality of circuit boards. HDI PCBs are now widely used in applications requiring smaller circuit boards, such as mobile phones, touchscreen devices, laptop computers, digital cameras, 5G network communications, autonomous systems in the automotive and aerospace industries, medical devices, and military applications, such as avionics and smart ammunition. To save space, HDI PCBs require the use of thin layers of dielectric materials with desirable thermomechanical and electrical properties at a low cost.
[0009] The PCB manufacturing process, which connects conductive and insulating materials, requires thermal deviations within a large temperature range of 250–300°C. The introduction of interconnecting conductors, including vias or microvias, also necessitates specific thermomechanically demanding processes. Almost all PCBs require that the conductive layer be manufactured using copper metal conductive sheets and wires. This introduces stringent requirements regarding the properties of dielectric base materials that can be used to produce PCBs containing copper conductive elements. Since conductive copper materials and dielectric materials can possess different thermomechanical properties, PCB manufacturing entails strict requirements regarding the thermomechanical properties of constituent materials deemed suitable for use as dielectric base materials. Consequently, only a small class of dielectric base materials with specific thermomechanical properties can be used in PCB manufacturing. If the material intended for use in the dielectric layer does not fall within the acceptable range of thermomechanical properties compatible with the copper conductive layer, PCB defects will occur. Therefore, the selection of dielectric materials with acceptable thermomechanical properties is a critical factor to consider in the field of PCB material design. The conventional need to match the thermomechanical properties of copper has resulted in the prioritization of thermomechanical design rules at the expense of the optimized electrical properties of the dielectric base material. Generally speaking, suitable dielectric materials should have a low tendency to expand when heated and be relatively rigid when subjected to mechanical force. These characteristics of low thermal expansion and high rigidity are believed to prevent excessive movement of the copper conductor layer during processing and prevent excessive deformation applied to interconnects during the PCB cycle life. However, limitations on the acceptable range of thermomechanical properties required for compatibility with the copper conductor layer have restricted the development of novel dielectric materials with optimized electrical properties that can be accommodated in existing PCB designs.
[0010] Most dielectric materials used to manufacture PCBs incorporate fiber reinforcements into a thermosetting resin system. The reinforcement typically takes the form of woven or non-woven glass fibers. Prepreg is a technical term used to describe woven or non-woven fabrics impregnated with a thermosetting resin composition. The terms A-stage, B-stage, and C-stage are used to describe prepregs in uncured, partially cured, and fully cured states, respectively. Prepreg is a flagship product of the PCB industry, and there are various types of glass fiber cloths used to create prepregs for PCB base materials, varying in glass fabric style, thickness, and dielectric constant. While most prepreg PCB base materials use glass fibers, other fiber reinforcements may also be used. A-stage or B-stage prepregs can be stacked to meet the required thickness, with metal foils, such as copper foil, stacked on one or both sides. The resulting assembly is then heated and compressed (often referred to as lamination) to form a metal foil laminate (e.g., single-layer or double-layer). During the lamination process, the thermosetting resin composition of the prepreg adheres to and cures the metal foil to form a copper-coated insulating layer. The C-stage prepreg or laminate is generally referred to as a "core" in the field. The core may be single-coated or double-coated with copper, and the copper may be etched to form a pattern for circuits.
[0011] Conventional PCB manufacturing processes typically involve constructing multilayer PCBs using a single-layer stacking process where cores and prepregs are stacked alternately. This contrasts with the HDI PCB manufacturing process, or build-up process, where layers are added sequentially and requires a new stacking cycle for each build-up. Prepreg is typically used for the build-up layers.
[0012] Typical thermosetting resins include epoxy resins, polyester resins, cyanate ester resins, phenol formaldehyde resins, BT resins, polyphenylene ether resins, and hybrids thereof. Additives such as flame retardants, curing agents, fillers, UV absorbers, coupling agents, tougheners, tack modifiers, antioxidants, and thixotropic agents can be introduced into the resin system to adjust the dielectric and physical properties of polymeric dielectric composite materials. Generally, premium products in the industry strive to balance the best electrical properties with the lowest expansion, but this can lead to manufacturing-related problems such as brittleness and reliability issues.
[0013] Conventional cured prepregs are composites formed from glass fibers, making them heterogeneous and anisotropic. Numerous properties, such as dielectric properties, the coefficient of thermal expansion (CTE), and Young's modulus in the x, y, and z directions (also known as tensile modulus), are affected. The issues of anisotropy and non-uniform dielectric properties cause "skew" in PCBs. Mechanical processes, such as drilling (mechanical or laser) and removing debris from holes, are difficult. Problems such as excessive heat accumulation, lower productivity, and lower reliability are also identified. Furthermore, the thickness of the glass fabric hinders the achievement of dielectric layer thicknesses of 25 μm or less on PCBs, thereby impeding the miniaturization process. The lack of availability of thin glass fibers combined with relatively high dielectric constants presents a particular challenge to the continuous miniaturization of PCBs.
[0014] Fine mineral or ceramic fillers may be added to prepreg compositions to adjust dielectric and physical properties. Hollow glass microspheres are used particularly to lower the dielectric constant. Before use, glass spheres are typically subjected to surface treatment to enhance the wettability of the spheres by the polymer matrix or to improve bonding for coupling reactions. U.S. Patent US 9,258,892 B2 (Crosley) discloses the use of hollow glass microspheres surface-treated with an alkaline solution to obtain a dielectric substrate layer having a low dielectric constant and a low dielectric dissipation factor. According to Crosley, compared to hollow glass microspheres applied to traditional surface treatments using acidic solutions, hollow glass microspheres treated with alkaline solutions achieved improved results (i.e., lower dielectric constant and lower dielectric loss tangent). Despite the use of different solutions, Crosley requires washing the glass spheres to modify the surface properties of the particles with alkaline solutions. Furthermore, Crosley does not teach the formation of films that can be handled and processed without a substrate. In fact, the dielectric formulations described by Crosley prove suitable for prepregs, as exemplified by the examples described in these patents.
[0015] Most multilayer PCBs are manufactured using prepregs. Accordingly, there are various known technologies regarding specific thermosetting resin compositions considered advantageous for use in prepregs. The general trend toward low-expansion prepregs is realized by using thermosetting compositions with high glass transition temperatures (Tg). However, these compositions tend to be brittle or exhibit solid-like behavior; therefore, they are expected to have insufficient film-forming capabilities and require a support such as glass fiber to be useful for PCB manufacturing. These thermosetting compositions are also likely unsuitable for the formation of films that can be transferred from one substrate to another, namely the formation of Type-3 curable films as defined in this application (see below). Even if the selection of a thermosetting composition can form a Type-3 film (often referred to as resin-coated copper or RCC) when coated on copper, such RCC has disadvantages for PCB manufacturing, including insufficient dielectric spacing control. Therefore, there is a need for thermosetting compositions capable of forming superior films that are more suitable for use in PCB manufacturing, including, for example, application as PCB base materials to replace cores and / or prepregs in conventional and HDI PCB manufacturing.
[0016] Anjinmoto Build-up Film (ABF), based on a phenoxy / epoxy thermosetting composition, for example as described in U.S. Patent US 6,805,958 B2 (Nakamura et al.), is a curable film used in the electronics industry that can be handled without a supporting substrate and is a common material for IC packages. However, it is rarely used in PCB manufacturing. U.S. Patent US 11,359,062 B1 (Amla et al.) describes a curable film based on a PHAE / epoxy thermosetting composition that has a dielectric constant similar to ABF but a lower curing Tg. However, both examples have limits of a dielectric constant (Dk) greater than 3 at 10 GHz and relatively high dielectric loss greater than 0.005, 0.010, or even 0.015.
[0017] The successful development of superior curable films capable of replacing conventional prepregs and / or cores for PCB manufacturing can enable PCBs with improved reliability, particularly when such cured film-based materials within the PCB possess low elastic modulus and low Tg, as described in U.S. Patent Application US 17 / 700,928 (the full disclosure thereof is incorporated herein by reference). Furthermore, recently, signal bands of information and communication devices such as PHS or mobile phones, and CPU clock times of computers, have reached the GHz band, and higher frequencies are being used increasingly frequently. The dielectric loss of an electrical signal is proportional to the product of the square root of the permittivity of the insulator forming the circuit, its dielectric loss tangent, and the frequency of the signal being used. Therefore, as the frequency of the signal being used increases, the dielectric loss also increases. Dielectric loss attenuates electrical signals and impairs signal reliability. To mitigate this damage, it is necessary to select a material as an insulator that has a low permittivity and a low dielectric loss tangent.
[0018] U.S. Patent US 7,541,408 B2 (Ohno et al.) describes an adhesive film having a very low dielectric constant for application as an adhesive sheet or cover-lay in a flexible printed circuit (FPC). Ohno’s film comprises a divinyl polyphenylene ether having a molecular weight of 70,000 to 300,000. FPCs generally have a structure in which a circuit pattern is formed on a copper foil laminated over a plastic film having heat resistance and insulation properties, represented by polyimide, and the circuit pattern is filled with a thermosetting insulating resin and then covered with another heat-resistant film. A film in which the uncured circuit pattern filling resin and the heat-resistant film are pre-integrated is referred to as a cover-lay film, and various types thereof have been proposed. Furthermore, FPCs are widely manufactured to have a multilayer structure for high-density packaging, and an adhesive sheet obtained by processing a thermosetting adhesive into a thin sheet has been used to form the multilayer structure. In FPCs manufactured by a method using a flexible copper clad laminate (FCCL), a coverlay film, and an adhesive sheet obtained by laminating copper foil onto a polyimide film, etc., the insulation between copper foil layers is secured through a polyimide film. However, a method to secure insulation between copper foil layers using a thermosetting adhesive used in the coverlay film or adhesive sheet, without using a polyimide film, etc., has been proposed in response to recent demands for high functionality of FPCs, particularly thinning. Flexible resin-coated copper (FRCC), in which an uncured thermosetting adhesive layer and copper foil are integrated, is used in this method. The base layer for PCB application requires a filler. However, it is known that the incorporation of fillers has a detrimental effect on film formation or film handling characteristics.Ohno emphasizes the difficulty of manufacturing an ideal curable film, particularly a Type 5 curable film as defined in the present application (see below), even when no filler is present in the curable film. The problem to be solved
[0019] Therefore, there is a need for a curable film that has a low dielectric constant, is easy to process, can form a thinner dielectric layer than currently available, and has excellent thermomechanical properties, while reducing the size of the substrate shape and increasing the frequency of the signal. means of solving the problem
[0020] In light of the above problems, the object of the present invention is to provide a composition for a curable film that is thin, easy to process, and has excellent dielectric and thermomechanical properties when cured. Another object is to provide a curable film suitable for replacing prepreg in PCBs, particularly multilayer PCBs and HDI PCBs. In particular, the object of the present invention is to provide a curable film that is release and transferable, has no or low tackiness, can be handled in a self-standing state, and can be used to produce a cured product having a low dielectric constant, a low dielectric loss tangent, and excellent heat resistance. These and other objects have been achieved according to the present invention.
[0021] The inventors have developed a novel class of curable films that can be used as dielectric base materials having a completely new range of thermomechanical properties previously taught as unacceptable for use as PCB base materials. The curable films of the present invention can be easily incorporated to manufacture relatively flexible yet rigid multilayer PCBs. Despite decades of teaching that dielectric base materials possessing both high CTE and low tensile modulus are impossible to use in PCBs, the inventors have surprisingly found that the materials of the present invention are commercially viable for use with copper conductive layers in PCBs. Indeed, the curable films of the present invention can be used to manufacture reliable multilayer HDI PCBs without defects during heat treatment, can be used in multilayer HDI PCB designs without defects in conductive interconnects during temperature deviations of hundreds of degrees Celsius, and can be used for many cycle lives without destruction of vias or microvias. Most surprisingly, the dielectric material of the present invention has been proven to enable the reliable fabrication of at least 14-layer multilayer HDI PCB structures, including microvias stacked directly over buried vias, which cannot be fabricated with any other dielectric material currently available. Thus, the novel dielectric base material of the present invention enables the reliable incorporation of previously unattainable design elements into multilayer HDI PCB structures, which was never possible before, and can withstand fabrication and thermal cycling without destruction of interconnections between conductive layers.
[0022] In particular, the inventors have discovered that when a rubber composition containing one or more diene rubbers is mixed with hollow glass microspheres of a suitable particle size or with a maleimide resin and a filler, e.g., silica and glass microspheres, a curable film (specifically, a Type 5 curable film as defined below in this application) can be obtained that is homogeneous, isotropic, easy to process, and free of cracks or voids even with a high load of filler. Such curable films are ideal for manufacturing dielectric layers having desirable thermomechanical and dielectric properties, particularly for multilayer PCBs and HDI PCBs, as they enable the manufacture of reliable and highly durable PCBs by reducing the PCB defect rate. The dielectric materials of the present invention are also useful as semiconductor interconnect (IC) packages, energy storage materials, and high-performance composites (e.g., reinforced plastics) for structural or non-structural applications (e.g., automotive, aerospace, and decorative applications), dielectric adhesives (used in the manufacture or bonding of electrical products), and other applications where the ability to precisely control electrical, mechanical, and thermal properties is important.
[0023] According to one embodiment of the present invention, a curable film composition or a curable film is provided, comprising hollow glass microspheres (HGM) having a specific particle size and a rubber composition. The rubber composition preferably contains one or more diene-based rubbers. In particular, the curable film comprises a rubber composition containing 2 to 65 wt% of HGM as component (A); and preferably a diene-based rubber having a weight average molecular weight of at least 60,000 as component (B). The HGM may be used as is. Specifically, the present invention surprisingly finds that, contrary to the teachings of the prior art and the knowledge of those skilled in the art, pre-washing of the HGM using an acidic or alkaline solution is not necessary to achieve desirable electronic properties (e.g., low Dk and low Df). Any component contained in the curable film composition or the curable film comprises other non-elastomeric polymers or oligomers, such as maleimide resin, hydrocarbyl thermoplastic polymer, and styrene maleic anhydride resin. According to one embodiment of the present invention, the curable film composition or the curable film comprises one or more fillers other than HGM.
[0024] According to another embodiment of the present invention, a curable film composition or a curable film comprising a filler, a rubber composition, and a maleimide resin is provided. In this embodiment, the maleimide resin is an essential component together with the filler and the rubber composition. The rubber composition preferably contains one or more diene rubbers. In particular, the curable film composition or the curable film comprises 10 to 80 wt% of a filler, such as silica and HGM, as component (A); a rubber composition containing a diene rubber preferably having a weight average molecular weight of at least 60,000 as component (B); and a maleimide resin having a solubility in at least 5 g / 100 ml of toluene at ambient temperature as component (C).
[0025] The diene rubber may be one or more selected from the group consisting of styrene-butadiene rubber (SBR), other styrene rubbers, e.g., styrene block copolymer (SBC), polybutadiene (PBD), polyisoprene (IR), butyl rubber (BR), ethylene propylene rubber (EPR), ethylene propylene diene monomer rubber (EPDM) which may or may not be partially or fully hydrogenated, and hydrogenated styrene block copolymer (HSBC).
[0026] The curable film composition of the present invention may not include a fabric or nonwoven fabric, or may include a fabric or nonwoven fabric. The curable film of the present invention may include a reinforcing layer or may include a reinforcing layer. In some embodiments, the curable film composition of the present invention may be used to impregnate a fabric or nonwoven fabric regardless of whether the fabric is anisotropic, semi-isotropic, or substantially isotropic.
[0027] According to one embodiment of the present invention, the rubber composition of the curable film composition (i.e., component (B)) further contains one or more liquid rubbers and / or low molecular weight diene-based rubbers. According to one embodiment of the present invention, the rubber composition (B) further contains polyphenylene ether or polyphenylene ether resin. According to one embodiment of the present invention, the rubber composition (B) further contains one or more radical initiators and / or curing agents.
[0028] According to one embodiment of the present invention, the curable film optionally comprises a flame retardant. According to one embodiment of the present invention, the curable film optionally comprises one or more auxiliary agents such as an adhesion promoter, a silane coupling agent, and an antioxidant.
[0029] According to one embodiment of the present invention, a method for manufacturing a curable film by processing a curable film composition into a film form is further provided. According to one embodiment of the present invention, since the curable film may be provided on a carrier substrate, a film assembly comprising a curable film and a carrier film may be obtained. The curable film may be released from the carrier film and / or transferred from the carrier film to another substrate while still possessing sufficient integrity to be handled in a self-supporting form. The carrier substrate may be disposable.
[0030] According to one embodiment of the present invention, a curable film is incorporated into an assembly and cured to obtain a cured product. In another embodiment, the curable film is obtained by curing a curable film coated with copper on one or both sides to create a core. Since such a core does not contain glass fiber reinforcement, it is a skew-free core. In another embodiment, the curable film replaces conventional prepreg in manufacturing a circuit laminate. In another preferred embodiment, a dielectric layer is obtained from the curable film. The dielectric layer can be used in a PCB.
[0031] The foregoing paragraph is provided as a general introduction and is not intended to limit the scope of the following claims. The described embodiments, along with additional advantages, will be best understood by referring to the following detailed description together with the accompanying drawings. Brief explanation of the drawing
[0032] FIG. 1a is an example i + n + i This illustrates an HDI PCB, where the middle is a glass-reinforced n-layer core, and the outer i The layers are prepreg-based layers. FIG. 1b illustrates an example of an arbitrary layer HDI PCB, wherein the middle layer is a double-sided glass reinforced core and the outer layer is a prepreg-based layer. FIG. 2 illustrates a 20-layer PCB stack-up structure used in an embodiment described in the present application, wherein a type 5 curable film is used as an adhesive layer instead of a prepreg layer. FIG. 3 illustrates an optical cross-section after thermal stress of a 20-layer PCB section having a structure as exemplified in FIG. 2, wherein the type 5 curable film E9 of the present invention is used as an adhesive layer. Figure 4 shows an optical cross-section after thermal stress of a 20-layer PCB portion having a structure as exemplified in Figure 2, wherein a comparative curable film C1 is used as an adhesive layer. Fig. 5 is 4 + 6 + 4 This illustrates an HDI PCB stack-up structure, wherein the middle layer is a glass-reinforced prepreg-based layer, and the four build-up layers are derived from the type 5 curable film E9 of the present invention. Fig. 6 shows Fig. 5 after thermal stress and 100 cycles up to 160°C. 4 + 6 + 4 This is an optical cross-section of an HDI PCB. FIG. 7a shows FIG. 5 during reflow measured according to IPC-TM-650, METHOD 2.6.7.2. 4 + 6 + 4 This illustrates the change in electrical resistance of the HDI PCB. FIG. 7b is FIG. 5 during thermal shock measured according to IPC-TM-650, METHOD 2.6.7.2. 4 + 6 + 4 This illustrates the change in electrical resistance of the HDI PCB. Specific details for implementing the invention
[0033] As used in this application, where terms such as “invention,” “the present invention,” or “the present invention” appear in both the heading and the text, they refer to the specific embodiments immediately following. These are not, in their entirety, extensively limiting, nor are they generally limiting to the various individual advancements in the art described in this application.
[0034] When a quantity, concentration, or other value or parameter is provided in this application as a list of ranges and / or values, it should be understood that this specifically discloses any range formed from any pair of upper and lower values, including endpoints, and includes all integers and fractions within the range, regardless of whether all ranges, integers, and fractions are disclosed separately. For example, a range of 1 to 10 includes and discloses 3 and 5.5. The scope of the invention is not intended to be limited to the specific values cited when defining the range.
[0035] The use of "one" or "one" to describe various elements and components is intended to provide a general meaning of the present disclosure. Unless otherwise evident, such terms should be interpreted as comprising one or more elements and components.
[0036] The terms “about” and “approximately” as used in this application refer to nearly identical to the referenced amount or value and should be understood to include ±5% of the specified amount or value. The term “substantially” as used in this application means all, nearly all, or the majority as understood by a person skilled in the art, unless otherwise defined. This is intended to account for reasonable variations from 100% that may actually occur routinely in industrial or commercial scale situations, for example.
[0037] As used in this application, "prepreg" refers to a fabric or nonwoven fabric impregnated with a thermosetting composition.
[0038] "Ambient temperature" or "room temperature" as used in this application refers to a temperature range of 15 to 25°C.
[0039] In the present disclosure, different curable films are classified into the following five types according to appearance, homogeneity, and processability.
[0040] "Type-1 curable film (sometimes simplified to "Type-1 film") refers to a coating or covering on a supporting substrate, and the film has a heterogeneous coverage rate and a heterogeneous shape characterized, for example, by different thicknesses and the presence of defects such as voids, empty spaces, lumps and cracks. A composition can form a Type-1 film if it can be applied on a supporting substrate even if it has high viscosity.
[0041] "Type-2 curable film (sometimes simplified to "Type-2 film") refers to a coating or covering on a supporting substrate, and the film is substantially uniform and homogeneous and does not have obvious defects such as voids, empty spaces, lumps and cracks.
[0042] "Type 3 curable film (sometimes simplified to "Type 3 film") refers to a coating or covering having a free surface and a contact surface that contacts a supporting substrate, wherein the film is substantially uniform and homogeneous; does not have obvious defects such as voids, empty spaces, lumps, and cracks; and can be transferred or released from the original supporting substrate to a new supporting substrate by bringing a new supporting substrate into contact with the free surface of the film. Pressure-sensitive adhesives and ironing transfer paper used on T-shirts and fabrics are examples of Type 3 films.
[0043] "Type-4 curable film (sometimes simplified to "Type-4 film") refers to a coating or covering on a supporting substrate, wherein the film is substantially uniform and homogeneous; does not have obvious defects such as voids, empty spaces, lumps, and cracks; and can be peeled off from the supporting substrate in its entirety as a single piece. Type-4 film differs from Type-3 film in that Type-4 film does not rely on another substrate to remove the film from the original supporting substrate and can exist at least temporarily without a substrate. Although Type-4 film can exist at least temporarily without a substrate after peeling off, such film cannot be processed without a substrate. As such, Type-4 film must be transferred to a new substrate for processing after being peeled off from the original supporting substrate. Anjinmoto build-up film (ABF) described in U.S. Patent US 6,805,958 B2 (Nakamura et al.) is an example of a Type-4 film.
[0044] "Type 5 curable film (sometimes simplified to "Type 5 film") refers to a coating or covering on a supporting substrate, wherein the film is substantially uniform and homogeneous; does not have obvious defects such as voids, empty spaces, lumps, and cracks; and can be peeled entirely from the supporting substrate in a single piece that can be handled without the supporting substrate. Thus, Type 5 film differs from Type 4 film in that Type 5 film can be handled, processed, or manipulated in a state where it is not supported and without a substrate. Type 5 film is essentially a film that is freestanding without being bonded to a base material (e.g., glass cloth, glass, or aramid nonwoven fabric) or supported by a substrate. Rogers 2929 bondply is an example of a Type 5 film. A film based on a PHAE / epoxy thermosetting composition described in U.S. Patent US 11,359,062 B1 (Amla et al.) is another example of a Type 5 film.
[0045] The film composition of the present invention described in this application is used to form a curable film that is a type 3, type 4, and type 5 film, preferably a type 4 and type 5 film, more preferably a type 5 film. The curable film can be used to replace prepreg and / or core in PCB manufacturing and to enable the manufacture of high-reliability microvias. The curable film has low insertion loss, which is because the cured film as a separation layer has a low dielectric loss tangent (Df) (e.g., < 0.005, < 0.004, < 0.003, < 0.002, < 0.0015, or < 0.0012, or about 0.001 or about 0.0009 when measured at 10 GHz), or a combination of low Df and intermediate low Dk (e.g., 2.8–3.1 when measured at 10 GHz), low Dk (e.g., 2.5–2.8 when measured at 10 GHz), very low Dk (e.g., 2.2–2.5 when measured at 10 GHz), or ultra-low Dk (e.g., 1.8–2.2 when measured at 10 GHz).
[0046] In a preferred embodiment of the present invention, the curable film composition or the curable film comprises a rubber composition containing hollow glass microspheres as component (A) and one or more diene-based rubbers as component (B). The content of hollow glass microspheres in the curable film is in the range of about 2 wt% to about 65 wt% with respect to the total weight of the curable film. The curable film may further comprise other particulate fillers other than hollow glass microspheres; the total content of fillers in the curable film is in the range of about 2 wt% to about 80 wt% with respect to the total weight of the curable film. The diene-based rubber preferably has a weight average molecular weight of at least 60,000. The rubber composition (B) may further contain an initiator and / or a curing agent. The rubber composition (B) may further contain other components such as liquid rubber, polyphenylene ether, and low molecular weight diene rubber. The curable film may further comprise other non-elastomer polymers, flame retardants, and other auxiliary agents.
[0047] In another preferred embodiment of the present invention, the curable film composition or the curable film comprises a filler, such as silica and hollow glass microspheres, as component (A); a rubber composition containing one or more diene-based rubbers as component (B); and a maleimide resin as component (C). The content of the filler is in the range of about 10 wt% to about 80 wt% in the curable film. The diene-based rubber preferably has a weight-average molecular weight of at least 60,000. The maleimide resin has a solubility in toluene of at least 5 g / 100 ml at ambient temperature and preferably has a weight-average molecular weight of at least 1,000. The rubber composition (B) of the curable film may further contain an initiator and / or curing agent and other components, e.g., liquid rubber, polyphenylene ether, and low molecular weight diene rubber. The curable film may further include other non-elastomer polymers, flame retardants, and other auxiliary agents.
[0048] According to one embodiment of the present invention, the curable film has a thickness of about 10 μm to about 250 μm. In one embodiment, the curable films may be stacked together to provide a greater thickness, and the stacked films may be cured by heat and pressure to a target layer thickness that may be greater than 250 μm.
[0049] [Rubber composition]
[0050] Diene rubber
[0051] In one embodiment of the present invention, diene rubber is an essential component of the curable film. The IUPAC defines an elastomer as a polymer exhibiting rubber-like elasticity. In other words, diene rubber is an elastomer that is a polymer having viscoelasticity and generally low Young's modulus and high elongation compared to other polymers such as engineering thermoplastic resins (e.g., nylon, PET). The inventors of the present invention have found that the elastomer is a key factor imparting excellent film-forming ability even with high loadings of fillers (e.g., HGM, silica, and other particulate fillers), excellent film handling characteristics, and, for example, the ability to manufacture Type 5 films. For example, it has been found that a composition containing an elastomer in an amount of 10 wt% or less in addition to other components can be used to manufacture a Type 5 curable film, but a composition containing all other components excluding the elastomer cannot be used to make a Type 1 or Type 2 film. The inventors have also discovered that when the elastomer is properly formulated, it imparts excellent heat resistance and excellent electrical properties to the cured material, thereby enabling the use of the elastomer as a component of a prepreg substitute for PCB manufacturing.
[0052] The mechanism is not known. However, without intending to be bound by theory, the inventors believe that the fact that the elastomer is an amorphous polymer at ambient temperatures of 15 to 25°C due to its low glass transition temperature (Tg) is a key factor. It has been found that a wide range of elastomeric materials can be used. For the purposes of this application, "elastomeric material(s)," "elastomeric(s)," and "rubber(s)" are interchangeable terms and include natural rubber, synthetic rubber, diene rubber (including diene rubber), and thermoplastic elastomers. The elastomeric materials used in the curable film compositions described in this application may also be bio-derived or bio-based instead of being petrochemically derived. That is, the chemical feedstocks used in rubber synthesis may be derived wholly or partially from bio-renewable sources.
[0053] Diene rubber is one of the preferred choices for the rubber composition (B) of the curable film of the present invention. Diene rubber is typically an amorphous polymer having a Tg in the range of 170 K to 250 K (-100°C to -25°C) and contains unsaturated sites that enable curability (i.e., crosslinkability) or co-curability with other components that can be incorporated into the curable film composition. Preferably, the diene rubber is at least one selected from the group consisting of styrene-butadiene rubber (SBR), other styrene-based rubbers, for example, styrene block copolymer (SBC), polybutadiene (PBD), polyisoprene (IR), butyl rubber (BR), ethylene propylene rubber (EPR), and ethylene propylene diene monomer rubber (EPDM). The rubber may be partially or completely hydrogenated. For example, hydrogenated styrene block copolymer (HSBC) may be used. It should be noted that other widely available rubbers, such as nitrile-butadiene rubber (NBR) and polychloroprene (CR), can be used to manufacture Type 5 films, but their use is limited in PCB-related applications due to the undesirable electrical and / or thermal resistance properties of the cured material.
[0054] In some embodiments, styrene-based elastomers are particularly preferred and may include random copolymers and block copolymers. In some embodiments, such suitable elastomers include elastomeric block copolymers comprising blocks (A) derived from alkenyl aromatic compounds and blocks (B) derived from conjugated dienes. The arrangement of blocks (A) and (B) includes linear and graft structures, including radial teleblock structures having branched chains. Examples of linear structures include diblock (AB), triblock (ABA or BAB), tetrablock (ABAB), and pentablock (ABABA or BABAB) structures, as well as linear structures comprising a total of six or more blocks of A and B.
[0055] In some embodiments, the compound used to provide block (A) is an alkenyl aromatic compound such as that disclosed in U.S. Patent US 9,265,160 B2 (Paul et al.). In some embodiments, the alkenyl aromatic compound is styrene.
[0056] In some embodiments, the conjugated dienes used to provide block (B) include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), sesquiterpenes (e.g., farnesene-based), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, specifically 1,3-butadiene and isoprene. Combinations of conjugated dienes may be used. The dienes may be derived from biorenewable sources. The block (B) derived from the conjugated dienes is optionally partially or completely hydrogenated.
[0057] An exemplary block copolymer comprising a block (A) derived from an alkenyl aromatic compound and a block (B) derived from a conjugated diene includes a styrene-butadiene diblock copolymer (SB), a styrene-butadiene-styrene triblock copolymer (SBS), a styrene-isoprene diblock copolymer (SI), a styrene-isoprene-styrene triblock copolymer (SIS), a styrene-(ethylene-butylene)-styrene triblock copolymer (SEBS), a styrene-(ethylene-propylene) copolymer (SEP), a styrene-(ethylene-propylene)-styrene triblock copolymer (SEPS), a styrene-ethylene-(ethylene-propylene) triblock copolymer (SEEP), a styrene-(ethylene-butylene) diblock copolymer (SEB), and a hydrogenated styrene farnesene copolymer (HSFC).
[0058] In some embodiments, the rubber may be selected from vinyl-linked elastomers. The vinyl-containing elastomer may have a high vinyl content (e.g., more than 70%, 80%, or 90% of a suitable constituent unit having vinyl groups), a medium vinyl content (e.g., 30% to 70% of a suitable constituent unit having vinyl groups), or a low vinyl content (e.g., less than 30% of a suitable constituent unit having vinyl groups).
[0059] In some embodiments, the rubber may be modified or post-modified with other reactive groups that can modify properties of the film after curing, such as assisting in the compatibilization of components in the curable film or promoting adhesion to the substrate. Examples of modification include rubber midblocks or other blocks grafted with maleic anhydride, and blocks modified with silicone. In some embodiments, the rubber may be substantially free of alkenyl or vinyl groups, for example, by substantial hydrogenation; nevertheless, the cured product of the curable film containing the rubber is still suitable as a PCB intermediate layer because the cured product does not exhibit notable creep.
[0060] An exemplary but non-limiting example of a commercially available elastomer that can be used as the diene rubber of the rubber composition (B) of the present invention is Kraton ® , Stereon ® , Septon ® , Hybrar ® , K-Resin ® , Styroflex ® Styrolux ® , Royalene ® Royaledge ® , Diene ® and Royalthrem ® Includes items with the product name called.
[0061] Although not specifically limited, the molecular weight of the diene rubber is typically > 10,000, preferably > 50,000 or > 60,000, more preferably > 100,000 or > 200,000. The rubber composition (B) of the curable film composition may contain one diene rubber or more than one diene rubber having different molecular weights.
[0062] The melt flow index of the diene rubber may vary and is not particularly limited as long as other factors such as the total filler load, other non-elastomeric components present in the rubber composition (B), the target rheology for the PCB compression lamination process, and the selection of the radical initiator in the rubber composition (B) are taken into account. Additionally, to replace the prepreg layer, the curable film may need to possess a rheology suitable for flowing and filling the copper wire of the underlying layer. Under these circumstances, a diene rubber having a higher melt flow rate is typically more preferable. For example, the melt flow index at 190–200°C in the range of 2–10 kg is preferably > 1, > 2, > 5, > 10, > 15, or > 20. In some embodiments, the melt flow index at 190 to 200°C in the range of 2 to 10 kg is about 1 to 200, 1 to 3, 3 to 50, 5 to 10, 10 to 20, 20 to 100, or 20 to 200.
[0063] In some embodiments, the amount of one or more diene rubbers contained in the rubber composition (B) of the curable film is in the range of about 55 wt% to about 100 wt% with respect to the total weight of the rubber composition (B) (e.g., 99 wt%, 90 wt%, 80 wt%, 70 wt%, 65 wt%, 60 wt%, and 55 wt%). In some embodiments, the diene rubber(s) are present in the rubber composition (B) in an amount of about 15 wt% to about 50 wt% with respect to the total weight of the rubber composition (B) (e.g., 50 wt%, 45 wt%, 40 wt%, 35 wt%, 30 wt%, 25 wt%, 20 wt%, and 15 wt%). In some embodiments, the diene rubber(s) may be present in the curable film composition in an amount as small as about 5 to 15 wt% (e.g., 5 wt%, 8 wt%, 10 wt%, and 13 wt%) with respect to the total weight of the curable film. In some embodiments, the diene rubber(s) may be present in the curable film composition in an amount ranging from about 20 wt% to 90 wt% (e.g., 20 wt%, 22 wt%, 30 wt%, 36 wt%, 46 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, and 90 wt%) with respect to the total weight of the curable film.
[0064] Initiator, Curing Agent
[0065] Since the film of the present invention is curable, components within the film may react and / or crosslink to "set" the film so that the curing material does not exhibit harmful creep behavior. In one embodiment, the curable film may be cured at a temperature of about 80°C to about 250°C, preferably about 120°C to about 250°C, more preferably about 140°C to about 220°C. In one embodiment, the film has a long working time below room temperature, so it has a sufficient "storage life" to be stored for weeks, months, or years after manufacturing and then used in the field (e.g., when cured for use in PCB manufacturing). It is not a requirement of the present invention that the curable film be completely crosslinked under the curing conditions for use. What is important is the desired rheological behavior of the cured product; for example, the curable film must be effectively creep-free when used as an insulating layer in a PCB. Since many diene rubbers have the potential to be heat-cured in the absence of any external curing accelerator or curing agent, in some embodiments of the present invention, particularly when the diene rubber of the rubber composition (B) is vinyl-rich, the curable film composition does not contain a curing agent. However, in a preferred embodiment, the rubber composition (B) of the curable film contains a radical initiator and / or a curing agent so that the curing behavior of the film is suitable and appropriate for use in a lamination process, for example, representative of PCB manufacturing. One important factor to consider in selecting a suitable radical initiator and / or curing agent is that they should not significantly activate the reaction during drying, particularly when the curable film composition is prepared with a solvent.
[0066] The rubber composition (B) may include a free radical source that can be thermally activated, for example, as an initiator or a curing agent. Examples of free radical sources that can be thermally activated include peroxides, azo compounds (e.g., α,α'-azobis(isobutyronitrile)), redox initiators (e.g., combinations of peroxide and ferrous salts such as H2O2), and azides (e.g., acetylazide). The free radical source may include at least one of a peroxide initiator, an azo initiator, a carbon-carbon initiator, a persulfate initiator, a hydrazine initiator, a hydrazide initiator, and a halogen initiator. The free radical source may include at least one of 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, and 1,4-diisopropylbenzene. The free radical source may include organic peroxides, for example, dicumyl peroxide, t-butyl peroxybenzoate, α,α'-di-t-butyl peroxy, diisopropylbenzene, and 2,5-dimethyl-2,5-di(t-butyl peroxy)-3-hexine. The free radical source may include a peroxide having a decomposition temperature of at least 50°C. Examples of peroxides include ketone peroxides (e.g., methyl ethyl ketone peroxide and cyclohexanone peroxide), peroxyketals (e.g., 1,1-bis(t-butyl peroxy)-3,3,5-trimethylcyclohexane and 2,2-bis(t-butyl peroxybutane)), hydroperoxides (e.g., t-butyl hydroperoxide and 2,5-dimethylhexane-2,5-dihydroperoxide), dialkyl peroxides (e.g., dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butyl peroxyhexine-3 and α,α'-bis(t-butyl peroxy-m-isopropyl)benzene), diacyl peroxides (e.g., octanoyl peroxide and isobutyryl peroxide) and peroxycarbonates (e.g., It includes peroxydicarbonates such as di(4-t-butylcyclohexyl)peroxydicarbonate.
[0067] The curing agent is not limited to any specific type and is generally useful for initiating the curing of the relevant polymer, oligomer, and / or monomer contained in the film composition. Examples include, but are not limited to, azides, peroxides, diazo compounds, sulfur, and sulfur derivatives. In a particularly preferred embodiment, the curing agent is peroxide-based. Suitable organic peroxides are dialkyl peroxide types (e.g., dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butyl peroxyhexine-3, α,α'-bis(t-butyl peroxy-m-isopropyl)benzene, di-t-butyl peroxide, di-t-amyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine-3 and 2,5-bis(t-butylperoxy)-2,5-dimethylhexane), peroxybenzoate types (e.g., t-butyl peroxybenzoate), peroxyacyl types (e.g., t-butyl peroxyacetate), hydroperoxides (e.g., t-butyl hydroperoxide and 2,5-dimethylhexane-2,5-dihydroperoxide), and diacyl peroxide types (e.g., lauroyl Suitable carbon-carbon type initiators may include, but are not limited to, peroxides, dibenzoyl peroxide types (e.g., dibenzoyl peroxide and di-(4-methylbenzoyl)peroxide), and ketone peroxide types (e.g., methyl ethyl ketone peroxide and cyclohexanone peroxide). Suitable carbon-carbon type initiators include, but are not limited to, 2,3-dimethyl-2,3-diphenylbutane and 3,4-dimethyl-3,4-diphenylhexane.
[0068] In a preferred embodiment, the rubber composition (B) also comprises a peroxide-based radical initiator. In one embodiment, a free radical initiator source having a decomposition half-life of at least 50°C and a 10-hour half-life is selected. In one embodiment, a free radical initiator source having a decomposition half-life of at least 100°C and a 10-hour half-life is selected. When used, the curing initiator is typically present in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the curable film. The loading amount and properties of the curing initiator can affect various properties such as the lamination properties of the curable film and post-lamination properties of the cured film, for example, the fluidity or rheology of the film, the time and temperature required to reach an appropriate or final cured state, and post-lamination (or post-curing) properties, for example, mechanical properties (e.g., elastic modulus), expansion properties (e.g., CTE), and electrical properties (e.g., dielectric loss tangent). Additionally, the shelf life (i.e., working time or shelf life) of the curable film may be partially dependent on the amount and selection of the initiator. In a preferred embodiment, the curable film of the present invention has a long shelf life of at least several weeks, several months, or several years at room temperature. In one embodiment, the curable film has a shelf life of at least one year at room temperature.
[0069] Liquid Rubber
[0070] It may be beneficial to include one or more liquid diene-based rubbers (referred to as liquid rubber or “LR” in this application) in the rubber composition (B) of the curable film for the purpose of controlling the rheological profile when pressure and heating are applied, such as when producing a PCB layer in a platen press. For example, for the purpose of replacing prepreg in a conventional PCB or HDI PCB manufacturing method, the curable film of the present invention can be produced with suitable curing and flow characteristics that allow copper wires and low-pressure regions to fill and flow and enable an acceptable dielectric gap in the final cured PCB assembly or subassembly. The inclusion of LR may also be used as a means to adjust the properties of the curable film in the cured or uncured state, for example, Young’s modulus, adhesion, electrical or expansion properties.
[0071] While diene rubber is an elastomeric solid at ambient temperature, LR has a measurable viscosity at ambient temperature or at a slightly elevated temperature and is in liquid or resin form. LR can be considered a low molecular weight analog of solid elastomers, because liquid rubber that does not have a sufficiently high molecular weight does not behave like a solid elastomer. Examples of liquid rubber that can be used to carry out the invention described in this application are generally the low molecular weight polymers described above and oligomers of the corresponding elastomeric rubbers. The molecular weight of LR may be in the range of about 1,100 to about 11,000, about 1,300 to about 11,000, about 3,000 to about 11,000, or about 10,000 to about 55,000. For example, most industrially available styrene-butadiene copolymer (SBC) and polybutadiene (PBD)-based liquid rubbers have an average molecular weight of less than 10,000. Liquid ethylene-propylene-diene-monomer (EPDM) rubber and liquid ethylene-propylene rubber (EPR) typically have an average molecular weight of less than about 50,000. Other examples include liquid butadiene rubber (LBR), liquid isoprene rubber (LIR), liquid farnesene rubber (LFR), liquid farnesene-butadiene rubber (L-FBR), and liquid styrene-butadiene rubber (L-SBR), which may have molecular weights ranging from about 1,300 to about 50,000.
[0072] The ideal content of solid diene rubber(s) and liquid rubber(s) in the rubber composition (B) of the curable film depends on various factors, including the viscosity of the liquid rubber, the stiffness of the elastomer, the total load of the filler, and considerations regarding whether the cured product or curable film obtained by curing the curable film is designed to replace the PCB core material or prepreg build-up material. If the rubber composition (B) of the curable film contains at least one LR having a high viscosity (e.g., > 100,000 centipoise at 40°C), the LR is present in an amount of about 20 wt% to about 60 wt%, preferably 40 wt% to 60 wt%, more preferably 50 wt% to 60 wt%, with respect to the total weight of the curable film composition. When the rubber composition (B) contains at least one LR having a low viscosity (e.g., < 100,000 centipoise at 40°C), the LR is present in a smaller amount of about 10 wt% to about 40 wt%, preferably 10 wt% to 30 wt%, more preferably about 10 wt% to 20 wt% with respect to the total weight of the curable film composition. The type 5 curable film can be obtained with a diene rubber to liquid rubber ratio in the range of about 1:5 to 1:0.1, preferably about 1:3 to 1:0.3. The specific combination of diene rubber(s) and liquid rubber(s) must be carefully checked for a given application of the cured product or curable film obtained by curing the curable film, such as a coverlay prepreg replacement or a core replacement, because, for example, if too much liquid rubber is incorporated into the composition, a type 5 film may not be obtained or the obtained curable film may have too much tackiness.
[0073] Preferably, the liquid rubber can co-cur with other components of the rubber composition (B). The LR may contain vinyl groups (i.e., 1,2 addition versus 1,4 addition of the diene) and may have a high vinyl content (e.g., more than 70%, 80%, or 90% of the suitable constituent unit having vinyl groups), a medium vinyl content (e.g., 30% to 70% of the suitable constituent unit having vinyl groups), or a low vinyl content (e.g., less than 30% of the suitable constituent unit having vinyl groups). The LR may be biologically derived or biologically based.
[0074] The liquid rubber may be a modified or grafted LR containing elements other than hydrocarbons, such as melanized, carboxylated, hydroxylated, acrylated, siliconized, or epoxidized LR containing maleic anhydride, carboxy, hydroxylated, acrylate, silicone, or epoxy functional groups. It should be noted that the inclusion of certain modified liquid diene-based rubbers may have a negative effect on the dielectric loss tangent of the cured film if incorporated in large quantities.
[0075] Commercially available liquid rubbers that may be incorporated into the rubber composition (B) include LRs manufactured by Cray Valley, Kuraray, Synthomer, and Evonik. Specific but non-limiting examples of suitable primarily hydrocarbon-only LRs include Ricon 300, Ricon 130, Ricon 131, Ricon 134, Ricon 154, Ricon 156, Ricon 157, Ricon 100, Ricon 184, Ricon 257, LIR-50, L-SBR-820, L-SBR-841, LIR290, Polyvest EP MV, and Litheneactiv ® 1000 and Lithene ®Includes ultra. Specific but non-limiting examples of modified LR include Ricon 130MA8, Ricon 130MA13, Ricon 130MA20, Ricon 603, Ricobond 1756, Ricobond 2031, Ricon CF MA8, Ricon MA6, Ricon 605 E, Polyvest EP MAT, Polyvest EP Mv, Poly BD 605E, Polvest ST-E 60, Polvest H, and LIR-410.
[0076] Polyphenylene ether
[0077] Poly(arylene ether) is generally referred to in the art as polyphenylene ether or poly(phenylene ether) or simply "PPE". The rubber composition (B) of the curable film described in this application may include one or more PPEs, including modified or functionalized PPEs.
[0078] The incorporation of PPE can adjust film properties, for example, in limited cases where film tackiness is high or release from a carrier is difficult. In addition to improving the handling properties of the uncured film, the introduction of PPE into the rubber composition (B) can also modify the properties of the resulting cured product (e.g., Tg, Young's modulus, and adhesive strength). In particular, the inventors have found that the incorporation of an amount of PPE or modified PPE material in an amount of about 5 wt% to about 30 wt%, more preferably about 7 wt% to about 15 wt%, based on the total weight of the rubber composition (B) of the curable film, significantly improves the release of the curable film from the carrier, reduces the tackiness of the curable film (e.g., when LR is present in the rubber composition (B)), and can even convert a composition formulation that could previously only produce a Type 3 film into a composition that produces a Type 4 or Type 5 film. The mechanism is not known; However, without intending to be bound by theory, the inventors believe that the PPE-based material is a rigid rod and acts as a reinforcing material that assists the elastomeric composition of the curable film, thereby facilitating the release of the curable film from the carrier.
[0079] The type of PPE-based material included in the rubber composition (B) is not particularly limited, but it is preferable that the PPE-based material be capable of co-curing with the diene elastomer or other components included in the rubber composition (B).
[0080] Poly(arylene ether) comprises a plurality of structural units of the following chemical formula 1:
[0081] [Chemical Formula 1]
[0082]
[0083] In Chemical Formula 1, R and R' are each independently hydrogen, halogen, primary or secondary C 1-7 , alkyl, phenyl, C 1-7 Aminoalkyl, C 1-7 Alkenylalkyl, C1-7 Alkynylalkyl, C 1-7 Alkoxy, C 6-10 Aryl and C 6-10 It is an aryloxy. In some embodiments, R is independently C 1-7 Alkyl or phenyl, e.g., C 1-4 It is alkyl; R' is independently hydrogen or methyl. PPE can be a homopolymer or copolymer, including graft or block copolymers. Various combinations of forms may be used.
[0084] Exemplary poly(arylene ethers) are poly(2,6-dimethyl-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dipropyl-1,4-phenylene ether), poly(2-methyl-6-allyl-1,4-phenylene ether), poly(di-tert-butyl dimethoxy-1,4-phenylene ether), poly(2,6-dichloromethyl-1,4-phenylene ether), poly(2,6-dibromomethyl-1,4-phenylene ether), poly(2,6-di(2-chloroethyl)-1,4-phenylene ether), poly(2,6-ditolyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diphenyl-1,4-phenylene ether), and It includes poly(2,5-dimethyl-1,4-phenylene ether). Useful poly(arylene ether) includes 2,6-dimethyl-1,4-phenylene ether units optionally combined with 2,3,6-trimethyl-1,4-phenylene ether units.
[0085] PPE can be functionalized to have reactive groups that enable participation in the curing behavior of a curable film, for example, by covalently incorporating them into a rubber-based matrix. In a preferred embodiment, the PPE oligomer or polymer has a reactive moiety or terminal group that enables the enhancement of properties of the rubber-based film. PPE can be functionalized to provide functional groups that can enhance adhesion between a conductive metal used to form a wiring layer and a dielectric layer, and improve other processing and performance characteristics. For example, PPE can be modified using a functional compound having (i) a carbon-carbon double bond or a carbon-carbon triple bond, and (ii) one or both of one or more carboxyl groups, including carboxylic acids, anhydrides, amides, esters, and acid halides. In one embodiment, the functional group is a carboxylic acid or ester group. Examples of polyfunctional compounds that can provide a carboxylic acid functional group include maleic acid, maleic anhydride, fumaric acid, and citric acid.
[0086] In particular, suitable functionalized PPE comprises the reaction product of poly(arylene ether) and cyclic carboxylic anhydride. Examples of suitable cyclic anhydrides are maleic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, and phthalic anhydride; more specifically, maleic anhydride or methacrylic anhydride. Maleinized PPE can be produced by the method described in U.S. Patent US 5,310,820A (Nelissen et al.) or is commercially available.
[0087] Examples of commercially available suitable modified poly(arylene ethers) include acrylate-terminated difunctional poly(arylene ethers) SA90 and SA9000 manufactured by SABIC, and PPE-MA (maleinized poly(arylene ether)) from Asahi. Examples of commercially available suitable unmodified poly(arylene ethers) include Blendex HPP820 from Chemtura.
[0088] In an embodiment of the present invention, the curable film comprises at least one PPE, an oligomer thereof, or a PPE and an oligomer thereof. It is preferable that one or more PPEs comprise two or more unsaturated groups, such as triple bonds, vinyl, alkenyl, and acrylate-type groups, at both ends of the molecular chain. For example, a suitable functionalized poly(arylene ether) comprises a reaction product of a poly(arylene ether) and a styrene-containing compound such that unreacted double bonds exist in the polymer produced after the reaction, and refers to Formula 2 below:
[0089] [Chemical Formula 2]
[0090]
[0091] In Chemical Formula 2, Y is selected from the group consisting of bisphenol A type, bisphenol F type, bisphenol S type, naphthalene type, anthracene type, biphenyl type, tetramethylbiphenyl type, phenol novolak type, cresol novolak type, bisphenol A novolak type and bisphenol S novolak type groups, and m and n are each independently natural numbers from 3 to 200.
[0092] [Filling]
[0093] Hollow Glass Microsphere (HGM)
[0094] The hollow glass microspheres (HGM) used in the curable film composition of the present invention are typically borosilicate microspheres made from soda-lime borosilicate glass. HGMs made from other types of glass may be used. The borosilicate microspheres contain mostly SiO2 and at least 1% B2O3, but the glass composition of the microspheres may vary to some extent depending on the starting material. An exemplary soda-lime borosilicate contains 80.7 wt% SiO2, 6.9 wt% Na2O, 10.3 wt% CaO, 2.1 wt% B2O3, and 1.9% impurities.
[0095] Various methods are available to manufacture the HGM used in the present invention. A common approach is to decompose the material at very high temperatures to form a gaseous composition within the droplet. The rapid expansion of the gaseous composition at high temperatures results in the formation of bubbles. Subsequently, the hollow droplet is rapidly cooled from the liquid state to form hollow microspheres. U.S. Patent US 3,699,050 (Henderson) discloses a dry gel process for manufacturing HGM. In this process, a glass-forming oxide solution is dried into a solid residue or gel and then ground to an appropriate particle size. The ground material is sieved into a narrow size range and then mechanically dropped through a hot furnace or spray tower. Chemically bound water in the gel appears to expand the particles as the surface melts, forming hollow glass microspheres. A blowing agent may also be used in the manufacture of HGM. US Patent US 4,904,293 (Garnier et al.) discloses the manufacture of microspheres having a high silica content, wherein starting glass is reduced to fine particles by grinding, optionally mixed with a foaming agent, and then passed through a burner flame at a temperature of 1500°C or higher to form molten hollow microspheres, and subsequently cooled to form solid hollow microspheres.
[0096] Alternatively, HGM can be prepared by mixing trace amounts of sulfur-containing compounds, such as sodium sulfate, with borosilicate glass. The mixture is then dropped into a high-temperature flame that melts the powdered glass and sodium sulfate. The melting of the sodium sulfate results in a decomposition reaction that releases trace amounts of sulfur gas, forming bubbles within the molten glass droplets. However, such HGM is generally undesirable for manufacturing circuit materials because sulfur-containing compounds or other such polar compounds tend to have adverse effects during the processing of circuit materials. Instead, the gas composition inside the microspheres is preferably inert, non-polar, sulfur-free gases, such as nitrogen, carbon dioxide, and oxygen. The content of undesirable polar compounds, such as sulfur dioxide, must be controlled to less than 1 wt%.
[0097] At least 95 wt% of the gas composition contained in the HGM used in some embodiments of the present invention is inert and consists mainly of nitrogen, followed by carbon dioxide, oxygen, and argon.
[0098] The hollow glass microspheres have a D50 of 30 μm or less. Preferably, the HGM has a D50 of less than 20 μm; more preferably, it has a D50 of 19.5 μm or 18 μm or less. Even more preferably, the HGM has a D50 of about 15 μm or less. Most preferably, the HGM has a D50 of about 12 μm or less and a D95 of about 19.8 μm or less. In some embodiments, the HGM contained in the curable film may have a D50 in the range of about 1 μm to about 30 μm (e.g., 2 μm, 4 μm, 6 μm, 9 μm, 11 μm, 15 μm, 18 μm, 20 μm, 26 μm, 28 μm, and 30 μm). In some embodiments, the HGM contained in the curable film may have a D95 in the range of about 2 μm to 45 μm (e.g., 3 μm, 5 μm, 6 μm, 9 μm, 11 μm, 14 μm, 17 μm, 22 μm, 28 μm, 33 μm, 36 μm, and 39 μm). In some embodiments, the HGM contained in the curable film may have a D99 in the range of about 1 μm to 45 μm (e.g., 2 μm, 5 μm, 6 μm, 9 μm, 11 μm, 15 μm, 19 μm, 24 μm, 28 μm, 30 μm, 36 μm, and 39 μm).
[0099] The particle size and particle size distribution of HGM must be carefully selected and controlled, especially when it is desirable to manufacture "thin" films. For example, HGM with an average particle size of about 35 μm and HGM with an average particle size of about 12 μm can both be used to manufacture Type 5 films, but the former was found not to be suitable for manufacturing thin films with a thickness of about 20 μm to 60 μm due to insufficient peel strength (e.g., less than 2 pounds per inch (lb / in)) attributable to the larger particle size.
[0100] The density of the hollow glass microspheres is 0.1 g / cc or more, preferably 0.2 to 0.6 g / cc, more preferably 0.3 to 0.5 g / cc. In some embodiments, the HGM can be used as supplied without special surface pretreatment, such as acid or alkali treatment. In some embodiments, the HGM can be modified with a surface functionalizing agent, such as a silane coupling reagent, to improve compatibility with the polymer matrix.
[0101] Commercially available hollow glass microspheres may be used. For example, HGM manufactured by Trelleborg Offshore (Boston), Emerson and Cuming, Inc., WR Grace and Company (Canton, Mass.) and 3M Company (St. Paul, Minn.), which are sold in various grades depending on density, size and coating, may be used.
[0102] Silica
[0103] The curable film of the present invention may include silica. Although not particularly limited by the type of silica, fused silica is preferred. The fused silica may have an irregular or spherical shape. The fused silica may have a D50 of about 0.1 to 50 μm, or about 0.1 to 10 μm, or about 0.1 to 1 μm.
[0104] The curable film may contain silica in a volume content of about 10 to 70 vol%, or about 20 to 60 vol%, or about 40 to 55 vol%, or about 10 to 40 vol% with respect to the curable film. The curable film may contain silica in a weight content of about 10 to 90 wt%, or about 20 to 70 wt%, or about 40 to 65 wt% with respect to the curable film.
[0105] Silica can be surface modified and / or functionalized. For example, functionalized fused silica can be prepared by reacting a silane containing a functional group. The functional group may include at least one of a (meth)acrylate group, a vinyl group, an allyl group, a propagyl group, a butenyl group, a styryl group, an aliphatic group, and a fluoride group.
[0106] Examples of (meth)acrylate-functional silanes are (3-acryloxypropyl)trimethoxysilane, n-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)methyldimethoxysilane, methacryloxypropyltrimethoxysilane, o-(methacryloxyethyl)-n-(triethoxy-silylpropyl)urethane, n-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropyltriethoxysilane, (methacryloxymethyl)methyldiethoxysilane, (methacryloxymethyl)methyldimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane. It includes methacryloxypropyldimethylethoxysilane and methacryloxypropyldimethoxysilane. Examples of vinyl-functional silanes include vinyltriacetoxysilane, vinyltriethoxysilane, vinyltriisopropenoxysilane, vinyltriisopropoxysilane, vinyltrimethoxysilane, vinyltris(2-methoxyethoxy)silane, vinyltris(methylethylketoxyimino)silane, (divinylmethylsilylethyl)triethoxysilane, docosenyltriethoxysilane, hexadecafluorododec-11-enyl-1-trimethoxysilane, hexenyltriethoxysilane, 7-octenyltrimethoxysilane, o-undecenyltrimethoxysilane, o-(vinyloxybutyl)-n-(triethoxysilyl-propyl)urethane, vinyltri-t-butoxysilane, vinyltris(methoxypropoxy)silane, vinylmethyldiethoxysilane, vinylmethyldimethoxysilane. It includes vinyldimethylethoxysilane, trivinylmethoxysilane, bis(triethoxysilylethyl)vinylmethylsilane, triethoxysilyl-modified poly-1,2-butadiene, and diethoxymethylsilyl-modified poly-1,2-butadiene. Examples of allyl-functional silanes include 3-(n-allylamino)propyltrimethoxysilane, n-allyl-aza-2,2-dimethoxysilacyclopentane, allyltrimethoxysilane, allyloxyundecyltrimethoxysilane, allyltriethoxysilane, and 2-(chloromethyl)allyltrimethoxysilane. An example of a propargyl-functional silane is o-(propagyloxy)-n-(triethoxy-silylpropyl)urethane. An example of a butenyl-functional silane is butenyltriethoxysilane.Examples of styryl-functional silanes include 3-(n-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane and styrylethyltrimethoxysilane. An example of a cyclopentadienyl-functional silane is (3-cyclopentadienylpropyl)trimethoxysilane. Examples of cyclohexenyl-functional silanes include [2-(3-cyclohexenyl)ethyl]trimethoxysilane and [2-(3-cyclohexenyl)ethyl]trimethoxysilane. The functional silane may include at least one methacrylsilane selected from γ-methacryloxypropyl methyldimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyldiethoxysilane, and γ-methacryloxypropyl triethoxysilane.
[0107] Other Fillers
[0108] The curable film composition of the present invention may include one or more fillers other than hollow glass microspheres and / or silica to further adjust the dielectric constant, dielectric loss tangent, coefficient of thermal expansion, thermal conductivity, and other properties of the cured product. The filler is preferably a particulate filler.
[0109] Examples of such particulate fillers include aluminum hydroxide, magnesium hydroxide, kaolin, talc, hydrotalcite, calcium silicate, beryllium oxide, boron nitride, solid glass powder, fumigated silica, silica powder, zinc borate, aluminum nitride, silicon nitride, silicon carbide, carborundum, corundum, alumina, magnesium oxide, zirconium oxide, mullite, titanium oxide, potassium titanate, barium titanate, strontium titanate, wollastonite, beryllia, alumina trihydrate, magnesia, mica, talc, nanoclay, and cenospheres, as described in U.S. Patent US 8,187,696 B2 (Paul et al.). In some embodiments, the filler is surface-treated with a silicon-containing coating. In some embodiments, a zirconate or titanate coupling agent is used to improve the dispersion of the filler in the polymer matrix and to reduce water absorption.
[0110] The curable film may include a thermally conductive filler. Examples of thermally conductive fillers include aluminum nitride, boron nitride, silicon carbide, diamond, nanodiamond, graphite, beryllium oxide, zinc oxide, zirconium silicate, magnesia, silica, or alumina.
[0111] [Malayimide Susie]
[0112] Maleimide resins are common additives for curable thermosetting compositions. The most widely used maleimides include bismaleimide (BMI). BMI is a class of maleimide resins containing two maleimide groups in its molecular structure. They are known for their high reactivity to amines and thiols, as well as high thermal stability and excellent chemical resistance. They are widely used as comonomers or resin additives in structural composites where high thermomechanical stability is required. Generally, commercially produced BMIs include 4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, and 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, for example, trade names BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-1100H, BMI-3000H, BMI-3000, BMI-4000, BMI-5100 manufactured by DKK (Japan). It includes BMI-7000H, BMI-7000, and BMI-TMI.
[0113] Although there are thousands of known bismaleimides and hundreds of commercially available bismaleimides, only a very limited number of bismaleimides are suitable for incorporation into curable film compositions intended for use as dielectric film materials after curing. In practice, the limited number of bismaleimide groups are generally used as additives or base resins in curable film compositions intended for use as dielectric layers, dielectric adhesives, and FCCL layer applications after curing. Suitable bismaleimides suitable for use as co-curable resins in uncured dielectric compositions are well known to those skilled in the art, for example, as taught in U.S. Patent US 10,822,527 (Tochihira et al.). Generally, BMIs in uncured dielectric compositions are used to improve the properties of the cured product prepared therefrom. BMIs known to those skilled in the art as useful for incorporation as resin additives or comonomers into curable film compositions for manufacturing dielectric electronic materials have the following properties:
[0114] (1) BMI that increases the adhesion of the composition and the peel strength of the cured product It is important to note that the BMI selected for use in uncured compositions to be used for manufacturing cured products in dielectric applications can increase the adhesion of the composition during the process from uncured to cured product. This increased adhesion is critical to the reliability of cured product manufacturing and also contributes to the peel strength of the cured product.
[0115] (2) BMI that reduces the CTE of the cured materialA person skilled in the art will be interested in the fact that thermomechanical stresses introduced by different CTEs between a conductive layer (e.g., copper) and any insulating or dielectric layer will contribute to a high defect rate during the thermal stress required to manufacture a device that relies on the bonding of the dielectric layer and the conductive layer. Therefore, only BMIs having known thermal and dimensional stability within the range required to process a curable composition into a cured product are considered useful as resin additives or comonomers in uncured systems where thermal stress makes the cured product unfeasible or unreliable.
[0116] (3) BMI that increases the decomposition temperature of the cured material: A BMI useful for an uncured layer intended for final use as a cured material must withstand thermal stress from manufacturing, solder-reflow, or other surface mount processes in addition to the thermal stress faced during the cured material's lifecycle. Only a BMI with sufficient thermal stability, meaning it can maintain electrical and mechanical properties even at high temperatures, is useful.
[0117] (4) BMI that has a high Tg and can increase the Tg of the hardened material:A person skilled in the art will be interested in the fact that a cured product produced from an uncured composition intended for use as a dielectric layer must have a sufficiently high Tg (i.e., > 200°C). The requirement of a high Tg is a fundamental teaching in the field of polymer technology suitable for dielectric material layers. Prior to the present invention, it was a key teaching in the field of polymer materials science that a high Tg is important for dielectric materials used, for example, in PCBs, because it determines the thermal stability of the material. Tg is the temperature at which a material changes from a hard glassy state to a soft rubbery state. In PCBs, for example, dielectric materials are subjected to elevated temperatures not only during soldering and assembly processes but also during normal use. If the Tg of the dielectric material is low, the material softens and deforms at these elevated temperatures, which can cause mechanical and electrical reliability problems. This can lead to issues such as interlayer separation, cracking, loss of insulation resistance, and catastrophic defects. Therefore, in current state-of-the-art technology, excluding the teachings of the present invention, high Tg dielectric materials are considered necessary to ensure that the material maintains its mechanical and electrical properties at the temperatures encountered during PCB manufacturing and use. A high Tg also enables the use of more aggressive assembly processes, such as reflow soldering, without compromising the reliability of the substrate. Therefore, a person skilled in the art would consider only BMIs having a high Tg as suitable resin additives for incorporation into uncured compositions intended for use in manufacturing cured dielectric films, cured dielectric layers, or other cured materials requiring the maintenance of thermomechanical and electrical properties.
[0118] (5) BMI that increases the Young's modulus of hardened materials:Young's modulus of a material is a measure of its stiffness or resistance to deformation under stress. It has been a core belief and fundamental teaching in polymer chemistry for use in dielectric layers that a high Young's modulus is desirable for cured dielectric products in multilayer structures because it helps maintain the dimensional stability of the dielectric layer during manufacturing and use. For example, when PCBs are subjected to thermal and mechanical stresses during manufacturing and use, dielectric materials are subjected to compressive and tensile forces. A high Young's modulus helps ensure that the dielectric material is not excessively deformed by these forces, which can lead to mechanical reliability issues such as cracking, interlayer separation, loss of insulation resistance, and catastrophic defects. Furthermore, a high Young's modulus helps ensure that the dielectric material maintains its thickness and dimensional stability during thermal cycling, which can affect the overall performance of the cured dielectric product in end-use applications. This is particularly important in HDI circuit boards, which are strictly controlled to allow for small dielectric thicknesses and closely spaced electrical lines. Therefore, prior to the present invention, it was known that a high Young's modulus is required for dielectric layers, particularly for use in PCBs, as it maintains the mechanical stability and reliability of the substrate and supports the use of high-density, high-performance designs. Accordingly, a person skilled in the art will select only BMIs that do not increase or at least decrease the Young's modulus of the cured product as resin additives or comonomers for incorporating into the uncured composition. This is especially true when the cured product is intended for use in a PCB, and even more so when the intended use of the cured product is a PCB using an HDI design.
[0119] (6) BMI having limited solubility in common organic solvents:It is well known in the art that BMI suitable for use as a comonomer or resin additive in uncured thermosetting compositions intended to produce cured products must have limited solubility in common organic solvents such as acetone, toluene, and methyl ethyl ketone. It is also known that solubility in polar aprotic solvents, e.g., N-methylpyrrolidone, dimethyl acetamide, dimethyl formamide, dimethyl sulfoxide, etc., is acceptable. When using BMI as a comonomer or resin additive in uncured compositions to produce cured products in dielectric applications, low solubility in solvents is desirable, as this ensures that the material maintains structural integrity and dimensional stability during processing and use. As is well known in the art, low solubility also makes it easier to control the thickness and uniformity of the dielectric layer, which is important for achieving desired electrical properties and performance. Additionally, low solubility can help reduce the risk of contamination of the dielectric layer during processing, which can negatively affect the electrical performance of the device. In contrast, if the BMI is highly soluble, it may be impossible to control the thickness and uniformity of the layer, and the material may dissolve or become contaminated during processing, which can lead to a reduction in the performance and reliability of the electronic device. High solubility in organic solvents, particularly aromatic solvents, is undesirable. In particular, for uncured thermosetting compositions intended to manufacture dielectric layers in electronic products, limited solubility in organic solvents is desirable because it helps ensure the stability and reliability of the composition before, during, and after curing due to the minimal release of water generated from ring-closing imidization during curing, as described, for example, in U.S. Patent US 4,924,005 (Dahms). Organic solvents such as alcohols and ketones are commonly used in manufacturing processes involving thermosetting dielectric layers, such as cleaning, solvent-based etching, and surface preparation.If BMI has high solubility in these solvents, it may dissolve and decompose, leading to changes in the material properties of the uncured composition and the cured product produced by the curing of the uncured composition. When BMI with high solubility in common organic solvents is incorporated into uncured thermosetting compositions as a comonomer or resin additive, it can result in dimensional instability, non-uniform curing, insufficient adhesion, low peel strength, and degraded electrical performance, as well as undesirable changes in Dk and Df. This can have a negative impact on the stability, reliability, and performance of the uncured composition, the curing process, and the cured product produced from the curing of the uncured composition. Undesirably, high solubility can also make the curing process less predictable and less efficient. High solubility in organic solvents, including acetone, ethanol, polar organic solvents, or aromatic solvents, can also lead to a loss of adhesion between the cured product produced from the uncured composition and other materials or layers of the end-use device, e.g., the substrate and metal wires of a PCB, which can result in undesirable Dk and Df, as well as interlayer separation, mechanical non-reliability, unpredictable thermomechanical properties, and degradation of electrical properties. Therefore, it is generally taught that only BMIs with limited solubility are suitable for use as comonomers or resin additives in uncured thermosetting compositions to prevent dissolution, degradation, and loss of adhesion, and to maintain the dimensional stability, electrical performance, and mechanical reliability of the cured product.
[0120] In summary, a person skilled in the art following the teachings of the prior art will select only a BMI having the following for incorporation as a comonomer or resin additive into an uncured thermosetting composition intended to produce a dielectric layer after curing: (1) the ability to increase the adhesion and peel strength of the cured product; (2) the ability to decrease the CTE of the cured product; (3) the ability to increase the decomposition temperature of the cured product; (4) the ability to increase the Tg of the cured product; (5) the ability to increase the Young's modulus of the cured product; and (6) high solubility in polar aprotic solvents such as N-methylpyrrolidone, dimethylacetamide, dimethylformamide, dimethyl sulfoxide, etc., but low solubility in common organic solvents such as acetone, toluene, methyl ethyl ketone, etc., is permitted. Accordingly, a comonomer or resin additive suitable for use in a curable composition is selected, wherein, where the cured product derived therefrom is intended to be used as a dielectric film, a person skilled in the art will select a cured product having a Tg of less than 180°C; We will diligently avoid selecting any BMI having a Young's modulus of less than 0.5 GPa; a CTE greater than 70 ppm / ℃; and high solubility in common organic solvents, for example, solubility in toluene greater than 15 g / 100 ml.
[0121] However, it was found to be contrary to the knowledge of those skilled in the art that commonly used BMIs, which are considered suitable for use in curable films for manufacturing dielectric layers, could not be incorporated into the curable film compositions of the present invention, and to be in direct contrast to, for example, the teachings of U.S. Patent 10,822,527 (Tochihira et al.). The inventors found that the incorporation of commonly used BMIs resulted in a composition that could not be cured into a film without introducing voids, holes, defects, crystalline deposits, phase separation, or other imperfections that made the curable film heterogeneous. For example, a curable film prepared using a composition containing diene rubber / liquid rubber and only 1 wt% of BMI 5100 resulted in phase separation or crystallization of BMI within the film.
[0122] Surprisingly, a BMI resin that is substantially soluble in toluene at a concentration of, for example, at least 10 g / 100 ml, at least 15 g / 100 ml, or even at least 20 g / 100 ml can be incorporated as a resin additive or comonomer into the curable film composition of the present invention, which produces a curable film without voids, defects, imperfections, phase separation, or thickness irregularities.
[0123] The preferred maleimide resin incorporated into the curable film composition of the present invention is amorphous and has a solubility in toluene at ambient temperature of at least 5 g / 100 ml, preferably at least 10 g / 100 ml, more preferably at least 15 g / 100 ml. The curable film comprising such maleimide resin exhibits a desirable high peel strength (e.g., > 6 lb / in) at an LP (low profile), VLP (very low profile), or HVLP (ultra-low profile) copper foil, an ultra-low dielectric loss tangent (Df) (e.g., < 0.002, < 0.0015, < 0.0012, or even about 0.001), and a low dielectric constant (Dk) in the range of about 1.9 to about 3.1. In one embodiment, the maleimide resin used in the curable film of the present invention has excellent miscibility with diene rubber and enables the production of a curable film (e.g., a Type 5 film) having excellent properties. For simplification, the maleimide resin used in the curable film composition of the present invention is referred to as "greasy MR" or "GMR". The combination of diene rubber(s) and GMR(s) has been found to be useful for producing suitable dielectric layers having low Tg and low modulus of elasticity in various applications, including thermosetting PCB base materials, which is contrary to the prior art teachings as described before and throughout this application.
[0124] In one embodiment, the GMR is capable of co-curing with diene rubber. In one embodiment, the GMR capable of co-curing with diene rubber has a solubility in toluene of greater than 10 g / 100 ml at ambient temperature. In one embodiment, more than one GMR is used.
[0125] The ratio of diene rubber(s) to GMR(s) is not particularly limited, as the components have typically been found to have excellent compatibility with one another. However, the diene rubber to GMR ratio is preferably in the range of 1:0.1 to 1:2, more preferably in the range of 1:0.2 to 1:0.8. In one embodiment, the diene rubber to GMR ratio is in the range of about 1:2 to about 1:1. In one embodiment, the diene rubber to GMR ratio is greater than about 1:1, or greater than about 1:0.9, or greater than about 1:0.8, or greater than about 1:0.7, or greater than about 1:0.6. In another embodiment, the diene rubber to GMR ratio is greater than about 1:0.5, or greater than about 1:0.4, or greater than about 1:0.3, or greater than about 1:0.2.
[0126] Suitable maleimide resins for the present invention include unsaturated points that enable a free radical curing method or other curing methods, and may be molecules, monomers, oligomers, or polymers and may be substantially partially cross-linked. Preferably, such maleimide resins contain two or more maleimide groups. Curable films also comprising GMR have been found to have improved adhesion, physical, thermal, and / or electrical properties.
[0127] In one embodiment, the GMR has a solubility for at least 5 g / 100 ml of toluene at ambient temperature. In one embodiment, the GMR has a solubility for at least 10 g / 100 ml of toluene, for example, greater than 20 g / 100 ml, greater than 30 g / 100 ml, or greater than 40 g / 100 ml. In one embodiment, the GMR has a solubility for more than 40 wt / wt%, 50 wt / wt%, 60 wt / wt%, 70 wt / wt%, or 80 wt / wt% of toluene at ambient temperature.
[0128] In one embodiment, the GMR has a molecular weight greater than about 600. In one embodiment, the GMR has a molecular weight greater than about 1,000. In one embodiment, the GMR has a molecular weight less than about 100,000. In one embodiment, the GMR has a molecular weight greater than about 1,000 and a solubility in at least 10 g / 100 ml of toluene at ambient temperature. In one embodiment, the GMR has a molecular weight greater than about 1,000 and a solubility in at least 20 g / 100 ml of toluene at ambient temperature.
[0129] Suitable GMRs may have structures represented by the following chemical formulas 3 to 5:
[0130] [Chemical Formula 3]
[0131]
[0132] [Chemical Formula 4]
[0133]
[0134] [Chemical Formula 5]
[0135]
[0136] In Chemical Formulas 3 to 5, n represents an integer from 1 to 100, and A, B, and C each represent a linker that enables solubility in at least 5 g / 100 ml or 10 g / 100 ml of toluene at ambient temperature. A specific but non-limiting example of Chemical Formula 3 is GMI 2300 manufactured by Shin A T&C (Korea).
[0137] With respect to the curable film, the exact molecular identity of linkers A, B, and C in Formulas 3 to 5 is not particularly limited. The presence of aliphatic chains (e.g., containing 10 to 50 carbon atoms) typically results in appropriate solubility and helps ensure sufficient miscibility with diene rubber. It is preferable that the linkers do not contain abundant polar groups, as polar groups can worsen miscibility and / or increase the dielectric loss tangent of the film after curing.
[0138] Specific but non-limiting examples of such suitable GMRs are those derived from dimeric or trimeric fatty acids and dimeric or trimeric fatty amines, e.g., C 36 Includes those derived from amines. Specific but non-limiting GMRs derived from dimeric fatty acids may be represented by the following chemical formulas 6 to 8:
[0139] [Chemical Formula 6]
[0140]
[0141] In Chemical Formula 6, n = 1 to 100.
[0142] [Chemical Formula 7]
[0143]
[0144] In Chemical Formula 7, n = 1 to 100.
[0145] [Chemical Formula 8]
[0146]
[0147] In chemical formula 8, n = 1 to 100.
[0148] The additional incorporation of other BMIs into the curable film composition is possible, provided that the incorporation does not serve to exclude the spirit of the present invention.
[0149] [Other Additives]
[0150] Flame retardant
[0151] To have fire resistance or flame retardancy, the curable film of the present invention or the cured product thereof preferably also comprises one or more flame retardants. In one embodiment, the curable film or the cured product thereof may have a UL-94 rating of V0, V1, VTM-0, or VTM-1. The flame retardant may be added to the curable film in an amount of about 5 to 30 wt% with respect to the total weight of the curable film. In the case of particulate flame retardants, particles having a D50 of less than 20 μm are preferred, less than 10 μm is more preferred, and less than 5 μm is more preferred. The flame retardant may be surface modified to enhance compatibility with other components of the curable film.
[0152] Flame retardants may be halogenated or non-halogenated; non-halogenated flame retardants are preferred due to environmental and health concerns. Non-halogenated flame retardants may be phosphorus-based or inorganic flame retardants. Examples of phosphorus-based flame retardants include melamine polyphosphate, aluminum diethyl phosphonate, DOPO derivatives including DOPO and DOPO-modified resins, triaryl phosphonates (e.g., triphenyl phosphate (TPP)), dimeric aryl phosphates (e.g., resorcinol bis(diaryl phosphate), bisphenol A bis(diaryl phosphate)), and phosphonate oligomers, homopolymers, and copolymers. Commercially available phosphorus-based flame retardants include Exolit® OP935 or Exolit® OP945, aluminum polyphosphate (available from Clariant Corporation), SPB100 or phosphazene (available from Otsuka Chemical Corporation), Altexia (available from Albemarle), PQ 60 (available from Chin Yee Chemicals), and Nofia® OL series, CO series, and HM series (products available from FRX polymers; Chelmsford, MA USA). Examples of inorganic flame retardants include ATH (aluminum trihydroxide) and MDH (magnesium hydroxide). Inorganic flame retardants are generally coated with organic materials to improve compatibility with the polymer matrix. Halogenated flame retardants such as Saytex 8010, ethylene-1,2-bis(pentabromophenyl), or BT 93 (available from Albemarle Corporation) may also be used.
[0153] <Supplements>
[0154] The curable film may include adjuvants that can be used to adjust the properties of the cured or uncured film. Such adjuvants include antioxidants to promote the stability of the curable film or its cured product in field use, adhesion promoters to improve bonding to copper foil, compatibilizers to improve the interaction between the filler and the rubber composition (B), and rheology modifiers to improve the flow properties of the curable film during heat pressing. Some adjuvants may serve more than one purpose, for example, reactive monomers or crosslinking agents may be used to alter the rheology profile of the curable film and to alter the physical properties of the curable film in the cured form by, for example, increasing the elastic modulus and decreasing the CTE.
[0155] The curable film may comprise a hydrocarbyl thermoplastic polymer or other polymers such as styrene maleic anhydride. In one embodiment, the curable film comprises an alpha-olefin and C 4-30 It may include a hydrocarbyl thermoplastic polymer comprising repeating units derived from cycloalkenes; a reactive monomer capable of free radical crosslinking to create a crosslinked network; a free radical source; and functionalized fused silica capable of chemically coupling to the crosslinked network. The hydrocarbyl thermoplastic polymer may comprise repeating units derived from at least one of cyclobutene, cyclopentene, cycloheptene, cyclooctene, cyclodecene, norbornene, and alkyl-substituted or aryl-substituted norbornene (e.g., 5-methyl-2-norbornene, 5-hexyl-2-norbornene, 5-phenyl-2-norbornene, 5-ethyl-2-norbornene, 4,5-dimethyl-2-norbornene, exo-1,4,4a,9,9a,10-hexahydro-9,10(1',2')-benzeno-1,4-methanoanthracene, exo-dihydrodicyclopentadiene, and endo,exo-tetracyclododecene). C 4-30The molar ratio of cycloalkene repeating units to alpha-olefin repeating units may be 6:1 to 0.5:1, or 6:1 to 1.5:1.0. The average molecular weight of the hydrocarbyl thermoplastic polymer may be 500 to 105,000.
[0156] In one embodiment, a co-curable adjuvant having a molecular weight greater than 500 is useful as an additive to the curable film composition of the present invention if it is soluble in toluene at an adjuvant level of at least 10 g per 100 ml of toluene at ambient temperature. Examples of such adjuvants include a co-curable polyphenylene ether such as SA9000, a co-curable vinyl-modified maleimide described in U.S. Patent US 11,066,520 (Hsieh), and a co-curable poly(styrene-co-glycidyl methacrylate).
[0157] The curable film may comprise a reactive monomer or a reactive crosslinking agent containing one or more unsaturated groups (e.g., vinyl, alkene, acetylene, acrylate, cyanate-ester, modified maleimide, and methacrylate). The use of the reactive monomer or crosslinking agent may serve as a rheology modifier for the curable film and simultaneously modify the elastic modulus, thermal expansion properties, and / or electrical properties of the cured form of the curable film. The reactive monomer may comprise trialyl (iso)cyanurate. The reactive monomer may consist only of carbon and hydrogen. The reactive monomer may be styrene-based. The reactive monomer may comprise a crosslinkable elastomer and may be a hydrocarbon resin diluent.
[0158] Crosslinkable elastomers are C olefins (e.g., ethene, propene, butene, butadiene, piperylene, and isoprene). 2-8It may be derived from at least one of alkenes and cyclic olefins (e.g., norbornene-type monomers containing unsaturated side groups such as 5-vinyl-2-norbornene), provided that the crosslinkable elastomer contains at least one of unsaturated and unsaturated side groups in the backbone. Examples of crosslinkable elastomers are derived from ethene, propene, and dicyclopentadiene. When a curable film comprises a crosslinkable elastomer containing repeating units derived from cyclic olefins, it may be distinguished from a hydrocarbyl thermoplastic polymer in that the hydrocarbyl thermoplastic polymer may not contain crosslinkable groups or the crosslinkable elastomer may have a lower weight-average molecular weight. For example, the crosslinkable elastomer may have a weight average molecular weight of 500 to 50,000, or 500 to 10,000, or 200 to 2,500; and the hydrocarbyl thermoplastic polymer may have a weight average molecular weight of 70,000 to 105,000. An example of a crosslinkable ethene-propene-dicyclopentadiene elastomer is TRILENE™ 65D, commercially available from Lion Elastomers (Geismar, La).
[0159] The curable film may include a hydrocarbon resin diluent. The curable film may include 0 to 50 vol%, or 5 to 40 vol%, or 10 to 30 vol% of a hydrocarbon resin diluent based on the total volume of the curable film. The addition of the hydrocarbon resin diluent may result in at least one of a reduction in minimum melt viscosity, an improvement in resin flow, and an improvement in leveling.
[0160] Hydrocarbon resin diluents may be saturated. Hydrocarbon resin diluents may comprise amorphous thermoplastic oligomers or polymers produced by the polymerization of unsaturated hydrocarbons. The hydrocarbon resin diluent oligomers used in this application may have a weight average molecular weight of 2,500 or less.
[0161] The hydrocarbon resin diluent is C 2-9 It may include a hydrocarbon resin diluent. The hydrocarbon resin diluent is an aliphatic C 2-9 Hydrocarbons or aromatic C 6-9 It can be derived from at least one of hydrocarbons. The hydrocarbon resin diluent is C 5-25 It may not contain repeating units derived from cycloalkenes. The hydrocarbon resin diluent may contain repeating units derived from cyclooctene.
[0162] Hydrocarbon resin diluents may include polybutene or oligomeric polybutene. Oligomers of C4 olefins (primarily isobutene) are commercially available in a wide range of weight-average molecular weights. Short-chain polybutene flows freely; medium-chain polybutene is sticky with honey-like consistency, while the longest-chain polybutene is a sticky semi-solid. Examples of polybutene include INDOPOL™ commercially available from INEOS Oligomers (London); and PANALANE™ commercially available from Vantage Specialty Ingredients, Inc. (Warren, NJ).
[0163] Hydrocarbon resin diluents may be derived from piperylene and optionally from aromatic repeating units. Hydrocarbon resin diluents may include C5 hydrocarbon resin diluents that can be prepared from piperylene or derivatives thereof, for example, cis / trans 1,3-pentadiene, 2-methyl-2-butene, cyclopentene, cyclopentadiene (CPD), and dicyclopentadiene (DCPD). Piperylene monomers and derivatives thereof may be cationically polymerized using a Lewis acid catalyst to produce oligomeric resins having low to high softening points. Since the C5 hydrocarbon resin diluent may be primarily aliphatic, it may be compatible with at least one of natural rubber, styrene-isoprene-styrene (SIS) copolymer, amorphous polyolefin (APO) (e.g., amorphous polyalpha-olefin (APAO)), polyolefin (e.g., low-density polyethylene (LDPE)), synthetic elastomer, and low-polarity cyclic-olefin copolymer (COC). The C5 hydrocarbon resin diluent may have a weight average molecular weight of 200 to 2,500. The C5 hydrocarbon resin diluent may have a softening point of 85 to 115°C, or 5 to 10°C (liquid grade). The C5 hydrocarbon resin diluent may be hydrogenated to reduce discoloration and improve thermal oxidation and UV stability. Examples of C5 hydrocarbon resin diluents include WINGTACK™ 10, WINGTACK™ 95, and WINGTACK™ 98, which are commercially available from Cray Valley (Exton, Pa.).
[0164] The hydrocarbon resin diluent is C 8-9 Hydrocarbon resin diluents, for example, may include aromatic repeating units. C 8-9 Hydrocarbon resin diluents can be prepared from coal tar or crude oil distillates (e.g., indene, methylindene, styrene, methylstyrene (e.g., alpha-methylstyrene) and vinyl toluene). Aromatic C 8-9Hydrocarbon monomers can be cationically polymerized using a Lewis acid catalyst to produce oligomeric resins with a weight-average molecular weight range. Aromatic C 8-9 Hydrocarbon resin diluents can have a higher melt viscosity and softening point (100 to 150°C) compared to C5 hydrocarbon resin diluents. Aromatic C 8-9 Hydrocarbon resin diluents are also compatible with various polymers.
[0165] The hydrocarbon resin diluent is, for example, as a blend or co-oligomer or copolymer thereof, a C5 resin diluent and C 8-9 It may include all hydrocarbon resin diluents. C5 and C 8-9 A curable film of a hydrocarbon resin diluent (e.g., as a blend or copolymer) may comprise 0 to 50 wt%, or 1 to 50 wt%, or 5 to 25 wt% of aromatic repeating units based on the total weight of the diluent. Aromatic C 8-9 Examples of modified C5 hydrocarbon resin diluents are Wingtack™STS, Wingtack™Extra, and Wingtack™86, commercially available from Cray Valley.
[0166] Hydrocarbon resin diluents may comprise blends, co-oligomers, or copolymers of any of the disclosed hydrocarbon resin diluents. For example, hydrocarbon resin diluents may comprise co-oligomers or copolymers derived from petroleum-based feedstocks such as aliphatic C5, aromatic C9, styrene, ethylene, propylene, and butadiene. Hydrocarbon resin diluents may comprise at least one of a styrene-ethylene butadiene-styrene copolymer or a styrene-propylene butadiene-styrene copolymer that may optionally be hydrogenated. An example of such a hydrocarbon resin diluent is REGALREZ™ resin commercially available from Eastman.
[0167] Hydrocarbon resin diluents can be distinguished from hydrocarbyl thermoplastic polymers in that at least one of the following applies: 1) the diluent may have a lower weight-average molecular weight, for example, the weight-average molecular weight of the diluent may be 60% or less of the weight-average molecular weight of the hydrocarbyl thermoplastic polymer; 2) the diluent may have a lower heat-distortion temperature point; 3) the diluent may have a lower glass transition temperature; and 4) the diluent may be reactive. One or more of these distinguishing features enable the hydrocarbon resin diluent to have a plasticizing effect on hydrocarbyl thermoplastic polymers and ceramic-filled versions thereof, thereby enhancing resin flow and reducing the minimum melt viscosity for the formulated system.
[0168] The hydrocarbon resin diluent may have a weight average molecular weight of 200 to 2,500, or 1,000 to 2,200, or 1,000 to 8,000. The hydrocarbon resin diluent may have a number average molecular weight of 150 to 6,000, or 200 to 2,200.
[0169] Other auxiliary agents that may be included in the curable film include colorants (e.g., dyes and pigments), plasticizers, curing retarders, curing accelerators, impact modifiers, UV protectants, heat stabilizers, light stabilizers, radical stabilizers, antistatic agents, preservatives, tougheners, rubber particles, lubricants, release agents, foaming agents, fungicides, processing aids, oxygen scavengers, nucleating agents, nanotubes, wetting agents, dispersants, enhancers, reinforcing agents, whiskers, and smoke suppressants.
[0170] [Method for manufacturing a curable film]
[0171] A method for manufacturing a curable film of the present invention is described below. In some embodiments, the curable film is provided on a substrate. Suitable substrates may be plastic films, metal foils, paper, fabrics, nonwoven fabrics, etc., having a release treatment optionally applied to one or both surfaces.
[0172] The method for manufacturing a curable film described in this application includes solvent casting, melt extrusion, lamination, and coating methods. Non-limiting examples of solvent casting, melt extrusion, lamination, and coating methods may be found, for example, in U.S. Patent Applications Publications US 2005 / 0133953, US 2009 / 0050842, US 2009 / 0054638, US 2009 / 0096962, and US 2010 / 0055356, the contents of which are incorporated by reference into this application. Further examples of solvent casting, melt extrusion, lamination, and coating methods for forming a film may be found, for example, in U.S. Patents US 4,592,885 and US 7,172,713, the contents of which are also incorporated by reference into this application.
[0173] In some embodiments, it may be possible to manufacture a curable film by a solvent-free process (e.g., melt extrusion), but a continuous solvent casting process (e.g., coating process) is a preferred method for manufacturing the curable dielectric film described in this application, because the solvent casting process can provide a film of high quality and uniform thickness.
[0174] A curable film according to the present invention can be prepared by coating a varnish composition onto a substrate, such as a carrier film and copper foil, and then drying to remove volatile solvents. A varnish composition in which the components of the curable film composition are dispersed in a solvent is essentially a precursor of the curable film. Suitable solvents include, but are not limited to, toluene, 1,3-dioxalane, ethyl acetate, and mixtures thereof. In some embodiments, the varnish composition is stable for several days (i.e., before the varnish gels due to the curing of specific composition components). In some embodiments, the varnish composition is stable for weeks, months, or years before gelation occurs.
[0175] Examples of coating methods include general coating methods and printing methods. Specific examples of coating methods include air doctor coating, bar coating, blade coating, knife coating, reverse coating, transfer roll coating, gravure roll coating, kiss coating, cast coating, spray coating, slot die coating, calender coating, dam coating, dip coating, and die coating. Specific examples of printing methods may include intaglio printing such as gravure printing, and stencil printing such as screen printing.
[0176] The drying conditions for removing the solvent are not particularly limited, but drying is preferably performed at a temperature appropriately adjusted within the range of 60 to 150°C depending on the solvent used in the varnish composition. Drying temperatures below 60°C are generally undesirable because the solvent tends to remain in the film. Additionally, low drying temperatures coupled with the volatilization of the solvent can cause condensation and phase separation or precipitation of the resin components. Drying at a prolonged temperature increase, particularly at temperatures above 150°C, is also undesirable because premature curing of the film may occur.
[0177] A typical solvent casting process comprises the steps of: (1) producing a varnish by dissolving and / or dispersing components (e.g., rubber, fillers, initiators, and other components, e.g., flame retardants, other organic polymers, oligomers, and molecules) in a solvent; (2) coating the varnish onto a substrate; and (3) producing a film on the substrate by evaporating / removing the solvent through drying (e.g., drying in a drying oven). The final thickness of the film can be controlled, for example, by passing the varnish through a slot die. Typically, for a casting process that produces a high-quality film, it is important that the polymer and other organic components are dissolved in the varnish solvent and that the filler components are well dispersed. The residence time and temperature profile of the drying oven will influence factors such as the amount of residual solvent retained in the film, and whether the film is partially cured or cured into a cross-linked polymer composition, or whether the composition remains as a mixture (e.g., still possessing thermoplastic properties). In some embodiments, the composition is a thermoplastic polymer composition after a film casting and drying process. In some embodiments, the composition is a thermosetting polymer composition after a film casting and drying process. In some other embodiments, the polymer composition is a cross-linked thermoplastic composition after a film casting and drying process.
[0178] In some embodiments, the curable film is manufactured or provided on a substrate such as a metal (e.g., copper, aluminum) foil, a disposable plastic carrier or release film, or other general carrier or release liner. Preferred non-limiting examples of plastic carriers or release films include polyethylene films, polypropylene films, polymethylpentene films, polyethylene terephthalate (PET) films, fluoropolymer films, polyethylene coated paper, polypropylene coated paper, and silicone releaseable paper. The carrier or release film may be treated with a release coating on one or both sides. In the case of a releaseable substrate using a plastic film as the base material, the thickness of the plastic film is preferably about 10 to 100 μm; whereas in the case of a releaseable substrate using paper as the base material, the thickness of the release liner is preferably about 50 to 200 μm. In some embodiments, the curable film manufactured on such carrier films or release films may be further laminated. In some embodiments, the curable film formed on such a carrier or release film may be further laminated with, for example, another release film or release paper as a protective layer so that both sides of the curable film are in contact with the releaseable carrier film. The carrier or release film may be removed later, and the curable film may be exposed and used.
[0179] In some embodiments, the curable film is coated directly onto a metal foil, such as copper or aluminum foil. Preferably, the copper foil is about 3 to 35 μm thick. The surface roughness of the copper foil may be standard HTE (High Tensile Elongation), "shiny," LP (Low Profile), VLP (Very Low Profile), HVLP (Ultra-Low Profile), or ANP (Nearly No Profile). The metal foil may be treated with an adhesion promoter, such as a silane coupling agent. In some embodiments, the curable film is coated directly onto the copper foil, and then a protective carrier or release film is laminated thereon. In some embodiments, the curable film may be coated with sputtered copper with a thickness of 0.5 to 5.0 μm via a physical vapor deposition process, for example. In some embodiments, the laminate is manufactured by laminating copper foil coated with the curable film of the present invention and then compressing them together via high-temperature roll lamination using a flat pressure press for batch processing.
[0180] In some embodiments, the curable film is non-adhesive to the touch. In some embodiments, the curable film is a Type 4 or Type 5 film having sufficient plasticity to be peeled off from a carrier film and placed on an object which may be a copper foil or sheet, a copper coating (etched, partially etched, or unetched), or a copper uncoated glass fiber core. In some embodiments, an assembly is formed, wherein the curable film on the carrier film (e.g., a Type 3 film) is placed on the free surface side of the substrate (i.e., the side opposite to the curable film side in contact with the carrier film); the assembly passes through a roll laminater; and then the carrier film is peeled off to leave the curable film on a new substrate which may be a copper foil or sheet, a copper coating (etched, partially etched, or unetched), or a copper uncoated glass fiber core. In some embodiments, the curable film is coated or uncoated with metal (e.g., copper). In some embodiments, the curable film is not reinforced (e.g., does not include a fabric or non-woven glass fabric or organic fabric).
[0181] [Characteristics of the cured product and curable film obtained by curing the curable film]
[0182] Here, “cured product obtained by curing the curable film” may be any product comprising the cured film obtained by curing the curable film of the present invention, or the curable film after being partially or completely cured. In some embodiments, the cured product obtained by curing the curable film and the curable film are substantially isotropic. In some embodiments, both the curable film and the component (B) of the component obtained therefrom are substantially miscible. The thickness of the curable film or the cured film obtained therefrom is typically in the range of about 0.2 Mil to about 16 Mil (i.e., about 5 μm to about 400 μm), preferably about 0.4 Mil to about 10 Mil (i.e., about 10 μm to about 250 μm), more preferably about 0.5 Mil to 4 Mil (i.e., about 12 μm to about 100 μm). In some embodiments, the thickness is approximately 10 μm, 12.5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, or 45 μm. In some embodiments, the thickness is approximately 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, or 105 μm. In some embodiments, the thickness is approximately 100 μm to approximately 200 μm. In some embodiments, the curable films may be stacked to achieve a thickness of approximately 2 Mil to approximately 10 Mil, or approximately 11 Mil to approximately 60 Mil.
[0183] The curable film may have a minimum melt viscosity of about 1,000 Pa·s to about 1,000,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 1,000 Pa·s to about 100,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 2,000 Pa·s to about 10,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 5,000 Pa·s to about 20,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 20,000 Pa·s to about 80,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 80,000 Pa·s to about 200,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the curable film may have a minimum melt viscosity of about 200,000 Pa·s to about 1,000,000 Pa·s when determined by rheological measurement at a strain of 0.1%. In some embodiments, the minimum melt viscosity occurs at about 80°C to about 200°C, or about 80°C to about 160°C, or 100°C to about 150°C when determined by rheological measurement at a strain of 0.1%.
[0184] In some embodiments, the curable film is a Type 3 film; in some embodiments, the curable film is a Type 4 film; and in some other embodiments, the curable film is a Type 5 film. In some embodiments, the curable film formed on the carrier film may be laminated or heat-pressed while the carrier film remains intact, and then the carrier film may be removed to reveal the curable film placed on a new substrate or the curable film obtained therefrom. In some embodiments, the free surface of the curable film, which is the surface opposite to the surface in contact with the carrier film, contacts the new substrate, and the assembly of the new substrate and the curable film on the carrier film thus formed passes through a roll laminater, after which the curable film may be transferred from the carrier film to the new substrate. In some embodiments, the curable film may be removed from the carrier or release film and placed on the substrate. In some embodiments, the curable film is not tacky to the touch. In some embodiments, the curable film is a type 5 film and has sufficient plasticity to be peeled off from the carrier film, then manipulated and placed on another object.
[0185] The curable film of the present invention has an excellent long shelf life. Currently available curable dielectric films tend to have a limited shelf life due to factors such as moisture absorption, chemical degradation, and aging. Many curable dielectric materials have a high affinity for water and can absorb moisture from the air over time. This can lead to changes in the electrical properties of the material, such as a decrease in insulation resistance and an increase in dielectric constant. Moisture in the curable film can also cause blistering during copper lamination; it can cause the curable film material to swell from the substrate or separate between layers, thereby causing electrical defects. Curable films for manufacturing dielectric materials can also be chemically degraded by exposure to light, heat, or other environmental factors. Curable films are highly susceptible to chemical degradation over time, particularly when stored above refrigeration temperatures. Chemical degradation can lead to changes in the electrical properties of the material, such as changes in dielectric strength and an increase in dielectric loss; Since dielectric materials can become brittle, this can lead to cracking and significant degradation of electrical and thermomechanical properties over time. Additionally, dielectric films can undergo aging, which is a time- and temperature-dependent change in material properties. Aging can occur due to exposure to environmental factors such as heat and radiation, or due to the inherent properties of the material. As dielectric material films age, their electrical properties may change, which can lead to performance degradation and eventually defects. In the case of curable films used for manufacturing dielectric layers, aging can cause uncured films to harden over time, thereby altering the rheological, electrical, and thermomechanical properties of the curable film.
[0186] For these reasons, commercially available curable films and curable prepregs require refrigerated storage at temperatures below 5°C to enable a shelf life of up to 180 days. Additionally, commercially available curable films typically require refrigerated storage in metal bags under humidity control to enable a shelf life of at least 90 days or 3 months. In contrast, the curable films of the present invention can achieve a shelf life of more than 90 days at ambient temperature without humidity control. Some embodiments have a shelf life of at least 6 months, at least 12 months, or at least 18 months when stored in a metal bag with or without humidity control, or when stored at ambient temperature without a metal bag.
[0187] A cured product obtained by curing the curable film of the present invention may have a peel strength of at least 2.2 lb / in for several grades of copper foil, including standard HTE (high tensile elongation) "shiny" copper with a tooth size of > 7 microns; LP (low profile) copper foil with a tooth size of 5.1 to 9.9 microns; VLP (very low profile) copper foil with a tooth size of > 2 microns and < 5 microns; HVLP (highly low profile) copper foil with a tooth size of > 0.5 microns and < 2 microns; and ANP (nearly no profile) copper with a tooth size of < 0.5 microns. In some embodiments, the cured product has a peel strength of about 3 to 10 lb / in for LP 1 oz copper. In some embodiments, the cured material has a peel strength of about 2.2 to 5 lb / in for 1 oz of ANP copper. In some embodiments, the cured material has a peel strength of about 4 to 10.5 lb / in for 1 oz of "shiny" copper. In some other embodiments, the cured material has a peel strength of about 2.9 to 9 lb / in for 1 oz of VLP copper. In some other embodiments, the cured material has a peel strength of about 2.6 to 8.5 lb / in for 1 oz of HVLP copper.
[0188] The Young's modulus of the cured product or curable film obtained by curing the curable film is in the range of about 0.01 GPa to about 10 GPa, preferably 0.01 GPa to 6 GPa, more preferably 0.01 GPa to 2 GPa, and even more preferably 0.01 GPa to 1 GPa. In some embodiments, the Young's modulus of the cured product is about 0.05 GPa, 0.1 GPa, 0.15 GPa, 0.2 GPa, 0.25 GPa, 0.3 GPa, 0.35 GPa, 0.4 GPa, or 0.45 GPa. In some embodiments, the Young's modulus of the cured product is about 0.5 GPa, 0.55 GPa, 0.6 GPa, 0.65 GPa, 0.7 GPa, 0.75 GPa, 0.8 GPa, 0.85 GPa, 0.9 GPa, or 0.95 GPa. In some embodiments, the Young's modulus of the cured product is about 1 GPa to about 2 GPa. In some embodiments, the Young's modulus of the cured product is about 2 GPa to about 3 GPa. In some embodiments, the Young's modulus of the cured product is about 3 GPa to about 4 GPa. In some embodiments, the Young's modulus of the cured product is about 4 GPa to about 10 GPa.
[0189] The glass transition temperature (Tg) of the cured product obtained by curing a curable film may be in the range of about -75°C to about 200°C when determined by thermomechanical analysis (TMA). Preferably, the cured product has a Tg of about -75°C to 150°C when determined by TMA. In some embodiments, the Tg of the cured product is in the range of about -75°C to about 30°C when determined by TMA. In some embodiments, the Tg of the cured product is in the range of about 0°C to about 150°C when determined by TMA. In some other embodiments, the Tg of the cured product is in the range of about 0°C to about 100°C when determined by TMA.
[0190] In some embodiments, the cured product obtained by curing the curable film has a thermal conductivity greater than 0.3 W / mk. In some embodiments, both the cured product obtained by curing the curable film and the curable film have a substantially isotropic coefficient of thermal expansion (CTE) when uncoated. The cured product may have an average CTE in the range of about 10 to 400 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured product has an average CTE of about 10 to 35 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured product has an average CTE of about 10 to 60 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured product has an average CTE of about 60 to 100 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured material has an average CTE of about 100 to 200 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured material has an average CTE of about 100 to 150 ppm / °C in a temperature range of 25°C to 260°C. In some other embodiments, the cured material has an average CTE of about 150 to 250 ppm / °C in a temperature range of 25°C to 260°C.
[0191] In some embodiments, the cured product obtained by curing the curable film has a dielectric constant (Dk) measured at 10 GHz of less than 3.5, preferably about 1.7 to about 3.2. In some embodiments, the cured product has a Dk measured at 10 GHz of about 2.5 to 3.2. In some embodiments, the cured product has a Dk measured at 10 GHz of about 2.85 to 3.2. In some embodiments, the cured product has a Dk measured at 10 GHz of less than about 2.45. In some embodiments, the cured product has a Dk measured at 10 GHz of about 1.7 to 2.2. In some other embodiments, the cured product has a Dk measured at 10 GHz of about 1.8 to 2.45.
[0192] In some embodiments, the cured product obtained by curing a curable film has a dielectric loss tangent (Df) measured at 10 GHz of less than 0.005. In some embodiments, the cured product has a Df measured at 10 GHz of about 0.004, 0.0035, 0.0033, 0.0030, 0.0028, 0.0026, or 0.0025. In some embodiments, the cured product has a Df measured at 10 GHz of about 0.0024 to about 0.0020. In some embodiments, the cured product has a Df measured at 10 GHz of about 0.0020 to about 0.0008. In some embodiments, the cured product has a Df measured at 10 GHz of about 0.0018 to about 0.0008. In some embodiments, the cured material has a Df measured at 10 GHz of about 0.0015 to about 0.0008. In some other embodiments, the cured material has a Df measured at 10 GHz of about 0.0014 to about 0.0008.
[0193] [Printed Circuit Board (PCB)]
[0194] In addition, a PCB comprising one or more dielectric layers obtained from a curable film described in the present application is also provided.
[0195] There are two main defect modes for vias on PCBs: (1) overstress and (2) low-cycle fatigue. Overstress can manifest spontaneously during the reflow process, where the assembly temperature is typically around 250°C. Several passes are generally required for reflow, and the combination of overstress and cycle fatigue can cause defects in microvias. The second defect mode is low-cycle fatigue (less than 1,000 to 10,000 cycles) attributed to operating conditions, which can range from -55°C to 135°C in extreme cases. In both defect modes, the key driver of insufficient reliability is considered to be the difference in the coefficient of thermal expansion (CTE) between the materials used for the metal (typically copper) conductor and the dielectric layer. Defects resulting from differences in the thermomechanical properties of the constituent materials of the PCB or IC substrate package can manifest in various ways, including cracks in copper interconnects (i.e., in plated through-holes and vias) and voids caused by interlayer separation. All these defect modes originate from the stress applied to the interconnects caused by the thermomechanical strain mismatch between the copper conductive layer and the dielectric insulating layer.
[0196] It has been widely taught for decades by those skilled in the art in the field of PCB design and PCB materials science, accepted as a core teaching of the prior art, and well known that PCB reliability is achievable only when composed of dielectric base materials having the lowest possible CTE for the purpose of matching the CTE of copper (approx. 17 ppm / °C) across the temperature range from ambient temperature to reflow or assembly temperature (typically about 250 to 260°C). It is also similarly taught by those skilled in the art and accepted as basic knowledge that higher Young's modulus (i.e., harder materials) is required to minimize thermomechanical stress occurring between the copper conductive layer and adjacent dielectric layers during the PCB manufacturing process and throughout the PCB product lifecycle. Since CTE and Young's modulus are correlated, PCB base materials that produce a low CTE also have a relatively high Young's modulus. The requirement that suitable PCB base materials possess a low CTE and high Young's modulus—close to or matching the CTE of copper—to minimize mechanical stress caused by CTE mismatch during the manufacturing, processing, and lifecycle required for PCBs has been a fundamental, enduring, and unchallenged teaching since the inception of the PCB industry. Therefore, dielectric materials suitable for use in PCB assemblies must have a low CTE as close as possible to the CTE of copper to minimize mechanical stress caused by mismatched expansion, possess a high elastic modulus to resist mechanical stress caused by thermal expansion, and possess a high glass transition temperature (Tg) to ensure that the dielectric material can withstand the PCB manufacturing process and subsequent device lifecycle without catastrophic defects caused by abrupt changes in thermomechanical properties occurring above Tg. This constitutes a fundamental teaching of PCB material design, a core element of the knowledge base of those skilled in the art, and an inviolable design rule for the selection and development of suitable PCB dielectric materials.These rules are particularly important for HDI PCB structures, where internal connections between conductive layers are more fragile and more susceptible to failure during manufacturing and throughout the HDI PCB lifecycle. The fragility of these internal connections, known as microvias, has resulted in additional limitations on acceptable dielectric materials and more restrictive design rules for HDI PCBs. For example, prior to the present invention, it was well known to those skilled in the art that PCB designs using stacked microvias located directly above buried microvias were not suitably reliable and should be avoided. Likewise, multilayer HDI PCBs with more than two to four layers cannot be reliably manufactured with any previously known dielectric material capable of withstanding both manufacturing and post-manufacturing thermal cycle test conditions.
[0197] In contrast to this well-known knowledge, the inventors have discovered that even though the dielectric layer of the present invention has a low Tg, low elastic modulus, and / or high CTE in some embodiments, such dielectric layer may be surprisingly suitable for use in the manufacture of reliable PCBs. Even more surprisingly, the inventors have discovered that previously unattainable PCB structures can actually be manufactured using the dielectric material of the present invention, which is designed and manufactured in complete contradiction to conventionally accepted dielectric material design requirements. That is, contrary to conventional teachings regarding PCB material design, reliable PCBs can be composed of dielectric materials having thermomechanical properties that exceed the generally accepted characteristic limits. The dielectric layer of the present invention has been found to be particularly useful for manufacturing multilayer PCBs and HDI PCBs, enabling higher reliability and increased interconnection density. In some embodiments of the present invention, the dielectric layer enables the use of stacked vias capable of withstanding assembly and having a high fatigue life under operating conditions. In one particularly remarkable example, an embodiment of the present invention was used to manufacture an HDI PCB structure having four layers of stacked microvias directly above embedded vias. The HDI PCB constructed according to an embodiment of the present invention withstood preliminary conditioning for manufacturing by 6× reflow at 260°C. Subsequently, the same HDI PCB structure withstood more than 100 thermal stress cycles at room temperature to 160°C without destruction of internal connections between the conductive layers. This highly complex arrangement of multilayer microvias directly above embedded microvias and stacked thereon cannot be reliably achieved with any other conventional PCB dielectric material.Any currently available dielectric material cannot be reliably incorporated into a multilayer HDI PCB structure of more than four layers without undergoing substantial destruction of internal connections of the conductive layer during the preliminary conditioning, manufacturing, and post-manufacturing thermal cycling as described above.
[0198] The characteristics that make the dielectric layer of the present invention ideal for PCBs, particularly multilayer PCBs and HDI PCBs, include combinations of low Dk and / or low Df and / or low skew that were previously unattainable in a dielectric layer configured as a base layer in a PCB, the ability to reach a dielectric thickness of less than 50 μm, improved dielectric spacing, enhanced adhesion to materials including metals such as copper, increased microvia reliability, and reduced insertion loss due to a combination of ultra-low Dk and low Df (e.g., < 0.0012, < 0.0015, < 0.002, or < 0.003). Additionally, because the dielectric layer of the present invention is a homogeneous and isotropic film, weaving effects that plague fabric-reinforced composites and cause skew or timing problems in high-speed digital transmission through PCBs can be eliminated.
[0199] In addition to chip packaging, standard double-sided and single-sided substrates, motherboards, sequentially stacked substrates, high and standard layer factor substrates, and flexible substrates, HDI PCBs used in IoT devices, camera modules, infotainment systems, mobile phones, tablets, and other consumer devices can benefit greatly from the use of these new materials. Furthermore, potential improvements in laser processability and increased throughput due to the absence of glass fibers, the ability to break dielectric thickness barriers, a potential 20–30% reduction in substrate thickness, weight reduction for the PCB, the ability to reduce stress on copper-plated vias, reduced Z expansion that increases microvia reliability, and improved crack resistance due to thickness control are some additional benefits that can be expected from the new materials of the present invention.
[0200] Although the invention has been described generally, further understanding may be obtained by referring to specific embodiments provided below for illustrative purposes only. These embodiments are not intended to be limiting.
[0201] Examples
[0202] [Manufacture of Curable Films]
[0203] Examples of curable films were generally prepared by mixing the components of a curable film composition (see Tables 1 and 2 for various curable film compositions of the comparative examples and embodiments of the present invention described in this application) in a high-speed rotary mixer and uniformly dispersing them in a suitable solvent (toluene, ethyl acetate, 1,3-dioxalane, or any mixture thereof) to prepare a varnish; applying the varnish onto a carrier film with a bar; then obtaining an assembly; and then drying the assembly in a drying oven to a residual solvent level of < 1%. Depending on the bar height, a curable film having a thickness of about 0.5 to 4 Mil could be obtained.
[0204] To manufacture a curable film for PCBs, a varnish was first prepared by mixing and dispersing the components of the curable film composition in a suitable solvent (toluene, ethyl acetate, 1,3-dioxalan, or a mixture thereof) using a Cowles mixer or a high-viscosity propeller. The solvent also serves to adjust the viscosity of the final varnish to approximately 2,700 centipoise (cp) at 22°C. Next, a varnish composition was continuously applied by a die coater to a PET-based carrier film with a width of 26" and a thickness of 2 mil to create an assembly. Then, the obtained assembly was passed through a four-zone drying oven. The line speed and zone temperature of the drying oven were adjusted so that the residual solvent level in the product was about 1% or less. The product was wound onto a roll and / or formed into a sheet with dimensions of 18" × 24". Using this procedure, dielectric curable films were produced on carriers with thicknesses of 3.5 mil, 2 mil, 1.2 mil, or 1.0 mil; the procedure can be adjusted to produce other curable films.
[0205] For the purpose of characterization, curable film piles were stacked together to build a thickness for electrical and thermomechanical testing, cured at a temperature of 160–250°C for approximately 1 to 4 hours, and compacted using a hydraulic flat-pressure press. The dielectric constant (Dk) and dielectric loss tangent (Df) at 10 GHz were obtained using a split post dielectric resonator. The coefficient of thermal expansion (CTE (ppm / °C)) was obtained using a thermomechanical analyzer (TMA) in accordance with IPC-TM-650 2.4.24.5. Young's modulus was measured at 30°C using a dynamic mechanical analyzer (DMA). The glass transition temperature (Tg (°C)) was obtained using a TMA. The peel strength (lb / in) values presented in Table 1 were measured using 1 oz standard HTE "shiny" copper foil; The peel strength (lb / in) values presented in Table 2 were measured using 1 oz HVLP copper foil.
[0206] E1 through E13, as shown in Table 1, were embodiments of the present invention comprising HGM and diene rubber (“DR”) as essential components of a curable film composition. Some of these embodiments also included liquid rubber (“LR”). C1 through C5 were comparative examples. The weight percentage of HGM, DR, or LR for each embodiment listed in the table was calculated based on the total weight of the curable film. Other curable film components as described in the present disclosure were included for balance.
[0207] All of the E1-E13 curable films of the present invention were Type 5 films. They were not sticky to the touch and possessed sufficient plastic-like properties to be easily peeled off from a disposable PET-based carrier and handled in a self-standing form. The cured products of the E1-E13 curable films all had low Df and very low or ultra-low Dk. In addition, the cured products of the E1-E13 curable films had a Young's modulus in the range of about 0.1 GPa to 1.4 GPa and an average CTE in the temperature range of about 26 ppm / °C to < 310 ppm / °C in the range of 25 to 260°C. Thus, as demonstrated in these examples, a wide range of mechanical, thermal, and electrical properties suitable as PCB dielectric materials can be achieved by specific combinations of HGM, diene rubber, and other components in the rubber composition (B) of the curable film of the present invention as described in this application.
[0208]
[0209] Comparative Example C1 did not contain HGM or any other filler. A Type 5 curable film was obtained and the cured product had sufficient dielectric properties (low Dk of 2.48 and low Df of 0.0018), but it failed the PCB reliability test described below and was therefore unsuitable for use in the manufacture of rigid PCBs or as a build-up layer for HDI PCB manufacturing.
[0210] Comparative Examples C2 and C3 did not contain sufficient HGM; the cured material had a CTE value exceeding 310 ppm / ℃. Similar to Comparative Example C1, the cured material could not be used as a reliable PCB in that it could not withstand a single thermal compression cycle required for preliminary conditioning or even PCB manufacturing, and could not withstand a thermal stress cycle after manufacturing.
[0211] As demonstrated by Comparative Examples C4 and C5, when the amount of HGM in the curable film was too high (exceeding 70 wt%), a substantially uniform and homogeneous curable film could be formed on the carrier, but it was merely a Type 2 film in that it could not be transferred or released and could not be completely removed from the carrier. In fact, the curable films of C4 and C5 were brittle and broke.
[0212] E14–E26, as shown in Table 2, were embodiments of the present invention comprising a filler (HGM and / or fused silica), a diene rubber, and an oily maleimide resin (GMR) as essential components of a curable film composition. The weight percentage of the filler, diene rubber, or GMR was calculated based on the total weight of the curable film. Other curable film components as described in the present disclosure were included for balance.
[0213] As shown in Table 2, the curable films E14–E26 of the present invention were all Type 5 curable films having excellent electrical properties and peel strength even when measured using less coarse copper foil. These examples demonstrated that Type 5 films could still be obtained even with high filler loadings of HGM and / or silica (e.g., > 65 wt%). Example E16 demonstrated that a Df of < 0.001 was achievable, for example, when the curable film also contained an extremely low Df hydrocarbon polymer or elastomer, e.g., a cyclic olefin copolymer-based elastomer. Table 2 indicates that any Dk of about 1.8 to about 3.2 can be produced, as the combination of DR, GMR, HGM, and silica can be adjusted to control the Dk and / or Df properties.
[0214]
[0215] [Manufacturing of Multilayer PCBs]
[0216] A 20-layer hybrid PCB using a curable film instead of a prepreg layer as an adhesive layer between copper foils was constructed with a basic stack-up structure detailed in Fig. 2. The PCB was fabricated using 5.0 mil standard FR4 (glass fiber reinforced dielectric) material, 1.0 oz copper foil as an internal copper layer, and a curable film each having a thickness of approximately 3.5 mil. A curable film was used as an adhesive layer instead of the commonly used glass-reinforced prepreg layer. The PCB panel had standard panel dimensions of 18" × 24" for mass production. Each internal copper layer was chemically etched to create desired copper features, and then the copper surface was prepared for lamination by chemically treating it using a standard PCB process.
[0217] PCBs were laminated in a vacuum press under predefined conditions suitable for curing a curable film. Typically, the material was exposed to a complete vacuum during a full press cycle reaching a temperature of approximately 210°C for a total time of about 3 hours under a pressure of up to 400 PSI.
[0218] Next, the 20-layer hybrid PCB was mechanically drilled, the holes were cleaned and plated, the outer layer circuits were etched, and the PCB was finished with a solder mask. Then, the individual PCB substrates were routed to manufacture the finished substrate. A cross-section was taken from the finished PCB and subjected to thermal stress and evaluation according to IPC-TM-650 2.6.8.
[0219] <Multilayer PCB of the present invention>
[0220] In an embodiment of the present invention, the curable film E9 of Table 1 was used as the curable film for a 20-layer hybrid PCB. As shown in FIG. 3, the PCB passed a thermal stress test and showed no voids or other signs of thermal stress.
[0221] <Comparison of Multilayer PCBs>
[0222] In this comparative example, curable film C1 of Table 1 was used as the curable film for the 20-layer hybrid PCB. As shown in FIG. 4, the PCB failed the thermal stress test in that voids appeared after thermal stress in the intermediate layer derived from curable film C1, which is free of HGM or silica fillers.
[0223] [Manufacturing of Multilayer HDI PCBs]
[0224] Having an offset from stacked microvias and buried via holes 4 + 6 + 4 The HDI PCB was fabricated through a stacking process. A detailed stack-up structure is shown in Fig. 5. The middle layer was a glass-reinforced high Tg FR4 material; in this embodiment, four layers of curable film E9 of Table 1, each having a thickness of about 3.5 mil, were added to both sides of the middle layer through a sequential stacking process. The HDI PCB was fabricated in a manner similar to the multilayer PCB described above, except that microvia cavities were formed using a laser process.
[0225] The type of microvia structure in which microvias are fabricated directly over buried vias is known to be "unreliable" because it is particularly vulnerable to thermal disturbances during fabrication and thermal stress testing. Consequently, since there are no suitable conventional dielectric materials that can be incorporated into multilayer HDI PCBs using this type of design, such designs are taught and not recommended by PCB industry associations, including IPC and HDP. However, there is a need for such structures in the industry, as a new class of multilayer HDI PCB structures becomes possible if these stacked-on-buried arrays can be reliably incorporated into multilayer HDI PCBs.
[0226] As highlighted in the optical cross-section shown in FIG. 6 and the electrical test results shown in FIG. 7a and 7b, the present embodiment 4 + 6 + 4 The HDI PCB successfully passed standard industrial tests for HDI PCB reliability evaluation. The HDI PCB fabricated using the curable film of the present invention passed a rigorous microvia accelerated test consisting of 6× reflow preliminary conditions at 260°C, and also passed thermal reliability standards after fabrication, including more than 100 thermal stress cycles at room temperature to 160°C while continuously monitoring the electrical resistance of the structure. In particular, all variations—i.e., microvias located directly above a buried via hole or slightly offset by about 3.0 mil to 8.0 mil from the centerline of a buried via hole but still above the buried via—met the IPC-TM-650, METHOD 2.6.7.2 requirement of a 5% maximum resistance change, as demonstrated in Figures 7a and 7b.
[0227] The foregoing description of the present invention provides methods and processes for manufacturing and using the invention so that a person skilled in the art can manufacture and use it, and such possibility is provided particularly with respect to the subject matter of the appended claims, which constitute part of the initial description. This description is provided in the context of specific applications and their requirements. Various variations of the embodiments will be readily apparent to a person skilled in the art, and the general principles defined in this application may be applied to other embodiments and applications without departing from the spirit and scope of the invention. Accordingly, the present invention is not intended to be limited to the embodiments shown, but should conform to the broadest scope consistent with the principles and features disclosed in this application. In this regard, specific embodiments within the invention may not represent all the advantages of the invention when considered broadly.
Claims
Claim 1 A curable film composition comprising: (A) an amount of filler in the range of 10 wt% to 80 wt% based on the total weight of the curable film composition; (B) a rubber composition containing at least one diene-based rubber and at least one liquid rubber; and (C) a maleimide resin having a solubility in at least 5 g / 100 ml of toluene at ambient temperature. Claim 2 The curable film composition according to claim 1, wherein the curable film obtained from the curable film composition has an average coefficient of thermal expansion of 100 ppm / ℃ or more in a temperature range of 25℃ to 260℃. Claim 3 A curable film composition according to claim 1, wherein the filler is at least one of silica and hollow glass microspheres. Claim 4 A curable film composition according to claim 1, wherein the maleimide resin has a solubility in at least 20 g / 100 ml of toluene at ambient temperature. Claim 5 In claim 1, the maleimide resin is a curable film composition having a molecular weight of more than 600. Claim 6 A curable film composition according to claim 1, wherein the rubber composition further contains at least one poly(arylene ether). Claim 7 A curable film composition according to claim 1, wherein the rubber composition further contains one or more initiators and / or curing agents. Claim 8 A curable film composition according to claim 1, wherein the curable film composition further contains one or more flame retardants. Claim 9 A curable film obtained from the curable film composition of claim 1. Claim 10 In claim 9, the curable film is a curable film having a storage life of more than 90 days at ambient temperature. Claim 11 A cured film obtained by curing the curable film of claim 9. Claim 12 In claim 11, a cured film having a glass transition temperature of less than 150°C. Claim 13 In claim 11, the cured film is a cured film having a dielectric constant of 1.7 to 3.2 at 10 GHz and a dielectric loss tangent of less than 0.005 at 10 GHz. Claim 14 In claim 11, the cured film has a Young's modulus of less than 3 GPa. Claim 15 An assembly comprising a substrate and a curable film of claim 9 on said substrate. Claim 16 A cured product obtained by curing the assembly of Clause 15. Claim 17 A printed circuit board comprising a dielectric layer obtained by curing the curable film of claim 9. Claim 18 A curable film composition according to claim 1, wherein the curable film composition does not contain epoxy resin.
Citation Information
Patent Citations
Film containing nano-particulate filler
KR1020160105971A
Curable resin composition
KR1020210137139A
